HMSA-Net: A lightweight transfer learning model for agricultural disease segmentation - Lin Shi; Xinyu Liu; Yafeng Wu; Yaguang Su; Li Zhao; Haiyang Zhang; Zhanlin Ji (Computers and Electronics in Agriculture, 2026)

The calcination mechanism and process optimization of montebrasite and CaSO4/CaCO3/Na2SO4 mixture - Xinyu Zhang; Yao Peng; Lin Zhang; Chongwen Li; Haiyan Wang; Qun Cui (Minerals Engineering, 2026)

Dynamic eco-corona formation drives the environmental fate of micro- and nanoplastics - Xinye Chen; Yiyi Zhu; Xinyu Liao; Qianmin Lin; Lei Zhou; Jun Wang; Xiaoyong Zhang (Gondwana Research, 2026)

Enhanced carbon capture and storage in the green microalga Chlamydomonas by heterologous expression of an engineered carbonic anhydrase - Yunlong Ge; Wanyi Zhang; Shuo Lin; Xinyu Mao; Keqing Liu; Wei Ma; Songlin Ma; Yanbo Liu; Zhanyou Chi; Fantao Kong (Bioresource Technology, 2026)

Wide-range and sensitive detection of LPS using a transporter@liposome enhanced electrochemical aptasensor - Xinyu Hu; Shukai Song; Ruyu Lin; Weidong Zheng; Haochen Qi; Lin Xu; Jian Zhang (Analytica Chimica Acta, 2026)

Evolution rule of pore structure and molecular structure in the process of coal adsorbing inert gas - Fei Gao; Zhe Jia; Wan Lin; Jidan Zhang; Xinyu Chang (Fuel, 2026)

Flower-centric temperature control: Optimizing osmanthus black tea aroma via environmental temperature regulation of floral vitality and enzymatic responses - Lin Xiang; Ahua Jie; Jian Lu; Jingjing Zhang; Dong Wang; Ying Zhou; Haowei Guo; Xinyu Feng; Weihong Huang; Guohua Ren; Qiang Chu; Ping Chen (Food Research International, 2026)

The efficient interfacial water evaporation enabled by a waffle-like double-network hydrogel evaporator in high-salinity seawater - Jinbu Su; Xinyu Dong; Weixin Du; Xuli Lin; Chenyi Shi; Xingxu Miao; Zifen Guo; Chengbing Wang (Desalination, 2026)

Porous activated carbon-supported tunnel-structured V2O5@VO2 for high-energy-density aqueous zinc-ion batteries - Guiquan Liu; Lin Sun; Qingjun Yang; Wanting Xie; Yu Liu; Xinyu Miao; Weidong Shi (Chemical Engineering Journal, 2026)

Extracellular polysaccharide-facilitated selenium nanoparticle assembly and metabolic reprogramming support efficient selenite biotransformation by ARTP-mutagenized Lactiplantibacillus plantarum Vse252 - Lihui Tan; Xinyan Wang; Lin Hu; Xiang Gen; Shirui Yu; Xue Li; Xinyu Yan; Bo He; Jun Zhang; Yongzhong Wang; Hengqian Lu (Bioresource Technology, 2026)

Operational challenges of ferry electrification: Scheduling under berth and charging limitations - Lin Lin; Orlando Rivera Letelier; Xinyu Wang; Andres Fielbaum (Sustainable Cities and Society, 2026)

Urban energy resilience under climate change: definition, quantification, and enhancement - Qinhui Lu; Shihong Zhang; Xinyu Wang; Wei Wang; Borong Lin; Zhe Wang (Sustainable Cities and Society, 2026)

STAGE: A spatio-temporal attention and graph embedding framework for modeling human mobility trajectories - Sizhe Zhang; Xinyu Zhang; Yunhan Jiang; Patrick Fowler; Michael Podgursky; Guangli Zhang; Kenan Li; Nan Lin (Spatial Statistics, 2026)

Unraveling the anti-listerial activity of noni fruit essential oil: Omics-based mechanistic insights and application in salmon preservation - Qiongping Hong; Jiamu Kang; Xinyu Li; Shanshan Zheng; Ming Yang; Lin Zhang; Yuyun Lu (International Journal of Food Microbiology, 2026)

Enhanced photodynamic inactivation against Listeria monocytogenes under blue light mediated by carbon dots derived from ‘Shatian’ pomelo peels for ready-to-eat sausage preservation - Ce Shi; Rui Yang; Xinyu Huang; Ziwei Liang; Layla A. Alahmari; Maha Abdullah Alwaili; Haiying Cui; Lin Lin (International Journal of Food Microbiology, 2026)

Protein and polyphenol structure transformation persuade “colloid-suspension” phase conversion in green tea beverages - Xinxin Wang; Lin Wang; Yunqing Liu; Yani Pan; Xinyu Feng; Wenzhi Ling; Xiangru Wang; Sitong Zhong; Yili Shen; Ranran Zhao; Yuefei Wang; Ping Chen; et al. (Food Chemistry, 2026)

Characterization of soybean proteins with various 7S/11S globulin ratios plus machine learning analysis for associating their corresponding physical and chemical functionalities - Yilai Wan; Xinyu Guo; Zhen Liu; Yanhong Lin; Guandi Chen; Yong Zhan; Shengwei Hu; Bing Wang; Chris Blanchard; Zhongkai Zhou; Guohua Zhao (Food Chemistry, 2026)

Enhanced elimination efficiency of rhamnolipid functionalized-nanoliposomes loaded with diacetyl against Listeria monocytogenes biofilms on food-contact surfaces and vegetables - Ce Shi; Yangyang Chen; Xinyu Huang; Ziwei Liang; Tariq Aziz; Shereen Magdy Korany; Fahad Al-Asmari; Amal A. Mohamed; Haiying Cui; Lin Lin (Food Control, 2026)

Temperature governs resistance assembly and dissemination in the freshwater plastisphere - Xinzhu Zhou; Xiaowen Lin; Xinyu Song; Mark Bartlam; Yingying Wang (Environmental Pollution, 2026)

Photothermal and humidity dual-responsive nanofiber actuator for adaptive human thermal management - Chaochao Du; Jing He; Xinyu Hu; Jiarong Zhu; Hong Lin; Desuo Zhang (Chemical Engineering Journal, 2026)

Sustainable mechanochromism and photochromism achieved by incorporating rhodamine into dialdehyde bacterial cellulose - Zheyu Shen; Qiuhao Yi; Bianjing Sun; Yalei Qiao; Xinyu Chen; Chenchen Qin; Lin Shi; Hongxia Qu; Chuntao Chen; Dongping Sun (Chemical Engineering Journal, 2026)

Mechanochemical engineering of interfacial M-Ov-Ni sites in CeZrO/Ni catalysts for reinforced low-temperature CO2 methanation - Xiaopo Niu; Yeben Liu; Yining Xia; Xinyu Hu; Zhengguo Wang; Chuqiao Song; Quanli Ke; Xiaoli Wei; Guokai Cui; Qingfa Wang; Lili Lin; Hanfeng Lu (Chemical Engineering Journal, 2026)

Genesis of the Jiawula Pb–Zn–Ag deposit in the Great Xing’an Range, NE China: constraints from fluid inclusions and S–Pb isotopes - Hongzhe Xie; Guiyuan Sun; Quzong Baima; Xinyu Gao; Ziwen Yang; Rui Tian; Lin Yang; Licheng Zhao; Zhiping Li (Journal of Asian Earth Sciences, 2026)

Development of a Recombinant Goose Parvovirus VP2 Neutralizing Epitope-Containing Region Vaccine Adjuvanted with IL-2 and FliC for Enhanced Immune Responses and Protection Against Challenge - Qing Wu; Xinyu Li; Jiaxin Li; Ziran Liu; Lin Bai; Lin Zhang; Shujing Xia; Di Wu; Yuhan Jin; Xinyuan Shen; Yu Gao; Jingming Wang; et al. (The Veterinary Journal, 2026)

Degradation of diclofenac via ascorbic acid-enhanced copper-catalyzed oxidation of sodium percarbonate system: Performance and mechanism - Zhenming Wang; Yajuan Cai; Jianying Wu; Xinyu Lin; Minfeng Wang; Lukai Zhuang; Zhongmin Fang; Guoqing Huang; Jing Zou (Process Safety and Environmental Protection, 2026)

Melatonin remodels gut microbiota and tryptophan metabolism to ameliorate methamphetamine-induced cognitive impairment - Lin Miao; Lisha Xu; Xue Yang; Yingjie Zhao; Qiaoqiao Liu; Xiaoxuan Zheng; Xinyu Zheng; Liu Liu; Jian Huang; Juan Li; Xiaofeng Zeng (Journal of Hazardous Materials, 2026)

To what extent do spheroidal carbonaceous particles (SCPs) indicate anthropogenic activities in coastal environments? - Zhenghao Xu; Feng Wang; Xinyu Li; Linxuan Lin; Tieyu Wang (Journal of Hazardous Materials, 2026)

Cold plasma treatment of noni juice: A dual strategy for flavor improvement and bioactivity enhancement - Xinyu Li; Jiamu Kang; Qiongping Hong; Shanshan Zheng; Lin Zhang (Food Chemistry, 2026)

Built-in electric field-driven d-band engineering in metal sulfide heterojunctions for high-efficiency electro-Fenton degradation of antibiotics - Xiangwei Zou; Yue Wang; Xinyu Wang; Lin Lin; Xiao-yan Li; Chitou Lei; Xiaojun Fan; Weng Ian Ieong; Qinfen Gu; Lianpeng Sun; Chao Yang (Chemical Engineering Journal, 2026)

Engineered norfloxacin-derived carbonized polymer dots for synergistic antibacterial and anti-inflammatory periodontitis therapy - Xinyu Jiang; Yu Deng; Jia Liu; Huan Chen; Hongyan Lin; Yu Zhong; Junjun Liu; Xinchan Liu; Bai Yang (Chemical Engineering Journal, 2026)

The plastisphere: from microbial pollution to biodegradable solution - Wenfang Lin; Kai Yang; Tao Lu; Xiaoxi Kang; Xinyu Xing; Ewa Korzeniewska; Natalia P. Ivleva; Feng Ju; Haifeng Qian; Li Cui; Yong-guan Zhu (ENGINEERING Environment, 2026)
Microplastic pollution is threatening planetary health and sustainable development. The microbiota colonizing microplastic surfaces, termed the plastisphere, has emerged as artificial niches that harbor both microbial risks and novel biodegradation potential. However, these two aspects of the plastisphere have often been investigated in isolation. In this review, we first elaborate on how microplastics act as vectors in facilitating the enrichment and dissemination of pathogens, antibiotic resistance genes (ARGs), and even virus, thereby causing serious microbial and ecological risks, and eventually impacting human health. To address the potential risks, the key plastic-degrading resources, the underlying mechanisms, and recent advances in biodegradation technologies are synthesized. Given the dual roles of plastisphere microbes, we therefore propose a two-dimensional screening framework to identify safer and more efficient degraders. This review aims to guide the selection or synthesis of safe and highly efficient degrading microbial consortia, thereby providing sustainable and eco-friendly strategies for mitigating plastic pollution.

Identification of Novel Polysaccharide from Myxococcus xanthus and its Function in Developmental Sporulation - Lin Liu; Songchen Jiang; Guirong Yang; Wenming Chang; Jin Lin; Lujun Zhang; Yijia Xu; Xinyu Li; Jie Bai; Lei Zhang; Xianfeng Ye; Yan Huang; et al. (Current Microbiology, 2026)

Preliminary Sea-Caught Versus Farmed Collection-Source Discrimination of Large Yellow Croaker Using Hyperspectral Features of Anatomical Regions - Xinyu Ai; Junjie Wu; Shengmao Zhang; Na Lin; Banghong Wei; Quanyou Guo (Fishes, 2026)
Large yellow croaker (Larimichthys crocea) is an economically important marine fish, yet rapid and non-destructive discrimination between sea-caught and farmed collection-source groups remains challenging. This study developed a fish-level analytical workflow integrating YOLO11n-seg instance segmentation with visible–near-infrared hyperspectral imaging to extract relative reflectance ratios from six anatomical regions. The analytical cohort comprised 258 unique fish, including 171 sea-caught and 87 farmed individuals. Source categories were assigned according to the original capture or cage-culture collection channels. Fish identity was used as the grouping unit in five-fold internal cross-validation, and classification performance was evaluated based on out-of-fold fish-level predictions. Logistic-regression models achieved AUC values ranging from 0.985 to 1.000 across the six individual anatomical regions. The combined six-region model achieved an accuracy of 0.996 (95% CI, 0.988–1.000) and an AUC of 1.000 (95% CI, 1.000–1.000) within the present cohort. For anatomical-region segmentation, the 20-image validation set contained 140 annotated instances. Bounding-box precision, recall, mAP@0.5, and mAP@0.5–0.95 were 0.976, 0.983, 0.981, and 0.700, respectively, while the corresponding mask metrics were 0.969, 0.976, 0.972, and 0.669. These results indicate that region-specific hyperspectral information can support highly accurate internal discrimination between the two collection-source groups and provide an interpretable basis for characterizing source-associated spectral differences. However, the source labels were not independently verified, potentially influential covariates were incompletely recorded, and no independent external cohort was available. Therefore, the present findings should be interpreted as internally validated collection-source discrimination rather than verified provenance authentication or evidence of external generalizability.

Marine polysaccharide-based multifunctional composite sponge for rapid hemostasis and enhanced infected wound healing - Yinuo Fan; Kaihua Liu; Chunxiao Wang; Xinyu Zhang; Ning Wang; Shuying Liu; Xianjiao Shao; Yuju Che; Panpan Pan; Lin Xia; Jingdi Chen (Marine Life Science & Technology, 2026)

In Vivo Wide-Field Mapping of Microvascular Dynamics in Orthotopic GL261 Gliomas by Super-Resolution Ultrasound Imaging - Zanhua Gao; Haoming Lin; Zhifan Yu; Huiqin Xu; Xin Chen; Xinyu Zhang; Yuanyuan Shen (Annals of Biomedical Engineering, 2026)

Taixinan contourite and mixed systems on the Gaoping Slope: Influence of intermediate water masses on the Taixinan canyon group - Zhi Lin Ng; Shan Liu; Kunwen Luo; Xinyu Xue; Zhixuan Lin; Tzu-Ting Chen; Ho-Han Hsu; Ming Su (Quaternary Science Reviews, 2026)

An explainable physics-aware deep learning framework with improved spatiotemporal dependence matrices and signal decomposition for multi-station uncertainty daily runoff simulation - Weiran Wu; Yan Kang; Haoyue Zhang; Libin Lin; Xinyu Zhao; Lingjie Li; Songbai Song (Journal of Hydrology, 2026)

Local polarization-piezoelectric field promotes water dissociation for efficient fluorinated pollutants defluorination - Yi Liu; Zhikui Zhou; Yuhang Xu; Xinyu Liu; Ying Zhou; Zixiang Lin; Ning Li; Li Yang; Xiaoyun Fan (Journal of Hazardous Materials, 2026)

Astaxanthin-loaded proliposomes as a novel strategy to enhance stability, bioaccessibility, and antioxidant activity - Hang Xu; Zhiwen Lin; Ruojing Liu; Xinyu Guo; Huiling Hao; Shuaiya Liu; Wentao Su; Yukun Song; Mingqian Tan (Food Bioscience, 2026)

Cosmetic exposure and hepatic steatosis: Investigating the role of metals and adipokines - Baihao Lin; Hao Deng; Yingjun Wu; Xiang Nie; Xinqi Jiang; Qiuyu Lin; Jiamin Wu; Shengya He; Yonglin Ye; Shuzhen Zhang; Zixiang Luo; Hang Hu; et al. (Food and Chemical Toxicology, 2026)

Impacts of urban open space environments on residents' health: A perspective on potentially toxic metals in dust - Yue Zeng; Qiang Ban; Junjie Yu; Changchun Qiu; Yajie Jiang; Xinyu Liu; Dian Lin; Shiqi Yan; Yunqin Li; Binxin Wu; Wei Yu; Rong Yu (Environmental Pollution, 2026)

Highly uniform Cu/Fe-LDH synthesized by a UNISON method for MRI-guided ferroptosis/cuproptosis therapy and immune microenvironment remodeling of tumors - Chunmei Chen; Bin Ren; Qingdeng Fan; Ya Huang; Xinyu Chen; Yurun Huang; Hang Yi; Guochao Wu; Jing Yang; Lin Huang; Jiaoyang Zhu; Haolong Ma; et al. (Chemical Engineering Journal, 2026)

Differences between human and rat 5α-Reductase 1 inhibition by phenolic disinfectants: Comparative kinetics and binding modes for neurosteroid synthesis - Xinyu Han; Wanyu Li; Yinghao Huang; Lisha Wang; Tianchi Zhao; Xishi Chen; Hao Lin; Yiyan Wang; Ren-shan Ge; Jianfeng Ma (Chemico-Biological Interactions, 2026)

Cover crop mixtures composed of three functional groups enhanced ecosystem multifunctionality in a subtropical citrus orchard - Xinyu Zou; Hailin Zhang; Jiaxin Ren; Huiping Ou; Lin Yang; Xiaojun Shi; Jie Wang (Plant and Soil, 2026)
Aims Cover crops enhance agroecosystem multifunctionality by modulating biodiversity, yet knowledge of their functional diversity remains limited. This study aimed to systematically evaluate the effects of cover crop species richness (SR) and functional group richness (FGR) on ecosystem multifunctionality (EMF) in citrus orchards. Methods This study assessed 33 cover crop planting schemes in citrus orchards in Southwest China, using six species arranged in gradients of SR (1, 2, 3, 4, 6) and FGR (1, 2, 3). Seasonal variations in soil properties, cover crop yield, and weed biomass were measured. Individual ecosystem functions and EMF across SR and FGR gradients were evaluated. The Random Forest Model and Structural Equation Modeling identified key drivers and mechanisms of EMF. Results (1) Cover crop polycultures suppressed weeds, increasing seasonal cover crop yield by 10–30% compared to single-species cover crops. They reduced soil temperature in spring, summer, and autumn while increasing it in winter. (2) SR and FGR exhibited quadratic correlations with EMF. FGR had a stronger influence, maximizing EMF (Mmde = 13.66) at a lower threshold (Tmde = 77%), compared to SR (Mmde = 12.86, Tmde = 84%). (3) Key EMF predictors included cover crop yield, soil alkali-hydrolyzable nitrogen, weed biomass ( p < 0.01), and soil organic matter, temperature, urease activity (0.01 < p < 0.05). SR and FGR directly enhanced EMF via cover crop yield (0.51) and indirectly via reduced weeds biomass (-0.33). Yield and weed biomass further acted through soil properties (temperature: 0.06, organic matter: 0.09, alkali-hydrolyzable nitrogen: 0.26). Conclusions FGR manipulation outperforms SR for enhancing EMF, offering a sustainable citrus orchard management strategy.

Metabolic Modelling Facilitates the Design of Synthetic Communities by Simplifying Natural Microbial Communities - Xinyu Lin; Shifeng Ding; Wanxin Li; Bingang Yang; Yahua Chen; Zhenguo Shen; Jiandong Jiang; Chen Chen; Xihui Xu (Environmental Microbiology, 2026)
Natural microbial communities generally have complex compositions and unclear metabolic interactions, posing constraints on their applications. Clarifying these intricate interactions within microbial communities is challenging for traditional experiment‐based methods. Here, we developed a simulation‐based approach to design synthetic communities (SynComs) by simplifying complex microbial communities through metabolic modelling. We constructed genome‐scale metabolic models (GSMMs) and curated them based on data obtained from straightforward experiments, ensuring these models precisely characterized metabolic features of each strain. By simulations utilizing multi‐strain metabolic models encompassing various strain combinations, we identified helper strains capable of enhancing the degradation efficiency of degrader strains and predicted optimal strain combinations that achieved a simplified community structure while maintaining high pollutant‐degrading efficiency. The simulations also unravelled cross‐feeding of glucosamine, amino acids and organic acids between the degrader and helper strains, which boosted the pollutant‐degrading efficiency of SynComs. Furthermore, helper strains rapidly degraded the toxicant intermediate, thereby alleviating its inhibitory effect on degrader strains. These predictions were further verified experimentally, demonstrating the accuracy and feasibility of metabolic model‐based simulations. Our study establishes a framework for designing simplified SynComs without sacrificing degradation efficiency and highlights the often‐underestimated role of microbial interactions in biodegradation.

Triterpene alkaloids from Buxus sinica and their anti-AChE activities - Liwu Lin; Xinyu Tao; Xiaocui Liu; Xingrong Peng; Minghua Qiu (Phytochemistry, 2026)

Global climate change reshapes nanoparticles' fate: rethinking risks and opportunities for soil-plant health - Xinyuan Bu; Shiyan Qiao; Danxing Yang; Xinyu Wang; Xin Liu; Luo Lin; Yuan Yang; Ali A. El-Keblawy; Kareem A. Mosa; Yaoyu Zhou (Environmental Research, 2026)

Synergistic activation of lithium slag using solid-waste-derived alkali and sodium sulfate: Towards high-performance low-carbon cementitious materials - Yannian Zhang; Lin Zhang; Qingjie Wang; Moncef L. Nehdi; Zhijun Li; Baoyuan Wang; Yunzhi Shang; Xinyu Dong (Sustainable Chemistry and Pharmacy, 2026)

Multi-sensor fusion for autonomous vertical docking in kilometer-scale deep-sea environments - Suohang Zhang; Lin Yu; Shipang Qian; Jiaxuan Song; Ziyang Wan; Ruiheng Liu; Lu Wang; Xinyu Fei; Canjun Yang; Yanhu Chen (Ocean Engineering, 2026)

CuxNiy/CeO2 catalyst for CO2 reduction in a creative CO2/H2 solid oxide fuel cell - Xuanyu Lin; Yiming Qin; Xinyu Feng; Hanzhen Liu; Zhenhang Lu; Xin Tang (Fuel, 2026)

Antiviral activity of marine fungal polysaccharide AVP141-A against Singapore grouper iridovirus (SGIV) in vitro and in vivo - Xinyu Liao; Xiaohui Zheng; Li Mo; Weifu Mo; Yijie Lin; Xiaoyong Zhang; Qiwei Qin; Jingguang Wei (Fish & Shellfish Immunology, 2026)

PFAS and adipokines: Decoding their roles in the risk of breast nodules and breast cancer - Mengya Xu; Xinyu Zhu; Yangyang Liu; Xuezhen Liu; Wanlu Liu; Baihao Lin; Yuyu Zheng; Kang Liu; Yue Feng; Nada Alhazmi; Shengtao Ma; Hao Chen; et al. (Environmental Research, 2026)

Tailored self-assembled molecule for efficient charge extraction and enhanced crystallization in wide-bandgap perovskite solar cells - Haojun Hu; Xianglang Sun; Xuke Yang; Zongbao Li; Peiyan Zhang; Xinyu Yu; Shi'ang Li; Zifan Lin; Dayu Liu; Ziyang He; Chuyun Deng; Longhui Zeng; et al. (Chemical Engineering Journal, 2026)

Crystallization-tailored polyamide triboelectric materials and device design for wind energy harvesting - Xintao Ma; Haoyu Yang; Xinyue Dai; Xinyu Zhang; Jing Xia; Chenglin Wang; Dongying Gong; Na Lin; Zihao Liu; Hao Liu; Suqin He; Miaoming Huang; et al. (Chemical Engineering Journal, 2026)

Synergistically enhanced nanofiber aerogels by directional freeze-drying and multiple hydrogen bond cross-linking for high-performance piezoresistive sensor - Xiao Su; Yufeng Bao; Zhe Tang; Asim Shahzad; Yaowei Luo; Xinyu Zeng; Zhifei Liang; Yangqing Wu; Lin Shu; Renbo Zhu; LinGe Wang (Chemical Engineering Journal, 2026)

Octopus-inspired photonic-electronic synergistic hydrogel tactile sensor for accurate and reliable health monitoring - Boqing Jia; Changxu Zhang; Yihe Zhao; Lan Yu; Yibo Lv; Gengyu Han; Xinyu Shi; Zhuorui Chen; Xuanting Lu; Jiaxiang Wang; Min Li; Guoxi Luo; et al. (Chemical Engineering Journal, 2026)

Dipole variability of subsurface marine heatwaves in the Bay of Bengal - Ying Zhang; Yan Du; Xinyu Lin; Yun Qiu (Climate Dynamics, 2026)

Targeting complement and coagulation cascades with Buyang Huanwu Decoction attenuates acute inflammation and enhances neuroprotection in spinal cord injury - Dezun Ma; Xinyu Xie; Yijun Ma; Hui Yan; Haoyuan Yin; Xue Tan; Yan Li; Xinpei Lin; Yuexin Huang; Xiang Wu; Zhihao Zhou; Chenglin Yang; et al. (Science China Life Sciences, 2026)

Simultaneous retrieval of hourly ground-level PM 2.5 and PM 10 from FY-4A/AGRI observations using multi-task deep learning - Xinyu Zhao; Lin Sun; Zaifei Wang; Xiaohang Shi; Jian Wang; Yulong Fan (International Journal of Remote Sensing, 2026)

Nighttime apple harvesting image enhancement based on a global–local feature fusion diffusion model - Liuchang Xu; Ting Ni; Fangshuo Zhou; Qingming Lin; Luyao Chen; Qianqian Luo; Kai Xia; Xingyu Xue; Xinyu Zheng; Sensen Wu; Zhenhong Du; Kai Fang; et al. (Computers and Electronics in Agriculture, 2026)

Application of antimony stable isotopes in revealing the source and migration of Sb in rivers - Xinyu Li; Guangyi Sun; Yunjie Wu; Yu Lin; Chenmeng Yang; Xinbin Feng (Water Research, 2026)

Experimental study on dynamic characteristics of marine soft soil foundations under minute-level intermittent loads from subway trains - Wei Huang; Lingling Li; Xinyu Lu; Lin Guo; Xibin Li; Xuanji Liu (Ocean Engineering, 2026)

Biodegradation of tetracycline antibiotics: Advances and insights into microbial resources, enzymatic mechanisms, and remediation potential - Aojie Lei; Mengyao Wang; Yaxin Pei; Qipeng Cheng; Hongyuhang Ni; Sen Yang; Hui Lin; Xinyu Liu; Hongge Chen (Journal of Hazardous Materials, 2026)

One-step retrieval of ground-level ozone concentrations from OMI hyperspectral observations using machine learning - Lin Sun; Zaifei Wang; Xinyu Zhao; Xiaohang Shi; Jian Wang; Yulong Fan (Journal of Cleaner Production, 2026)

Aggregation caused quenching of dual-emission nitrogen-doped carbon dots for visual quantitative and ratiometric detection of pesticide residues - Xinyu Luo; Dejin Lin; Jingqi Wang; Yihao Zhang; Xinru Liu; Sineng Gao; Da Chen (Food Chemistry, 2026)

Porous-interconnected cell microspheres-based 3D bioprinting of vascularized high-cell-density tissues with channel-pore networks - Xueping Wang; Xinyu Zhang; Lin Gu; Menglin Liang; Yudong Yao; Yuan Jin; Lei Shao (Chemical Engineering Journal, 2026)

Removal of lead and ammonia via microcapsules-based microbial induced carbonate precipitation (MC-MICP): Performance and mechanism - Zhong-Fei Xue; Chao Xu; Wen-Chieh Cheng; Lin Wang; Liang Xu; Tingting Deng; Xinyu Xu (Chemical Engineering Journal, 2026)

High-efficiency enzymatic conversion of cellulose to starch by strengthening glucose-utilization bypass - Yuanyuan Zhang; Menglong Chen; Yating Wang; Zhenwei Xiong; Keqiang Xu; Xinyu Liu; Hui Lin; Quanjun Liu; Hongge Chen (Bioresource Technology, 2026)

Mariana trench-derived fungal polysaccharide AVP214–1 inhibits Singapore grouper iridovirus infection in vitro and in vivo - Xinyu Liao; Gaoqi Yu; Xiaohui Zheng; Yanqi Zhao; Siting Wu; Weifu Mo; Yijie Lin; Xiaoyong Zhang; Zhuang Han; Qiwei Qin; Jingguang Wei (Aquaculture, 2026)

Nitrogen-removal collapse and recovery: Integrative meta-omics insights into seasonal microbiome dynamics and cold-adaptive mechanisms in a full-scale activated sludge system - Limin Lin; Xinyu Zhu; Xiaoxing Lin; Ze Zhao; Hui Wang; Huizhen Yan; Feng Ju (Water Research, 2026)

Redox-pathway steering enables photocatalytic valorization of CO2 and 1-phenylethanol with record quantum efficiency - Xinyu Xu; Jia Zhou; Meiyan Guo; Wanxiang Yang; Bo Su; Meifang Zheng; Xiahui Lin; Xue Feng Lu; Yidong Hou; Guigang Zhang; Wei Lin; Sibo Wang (Science Bulletin, 2026)

Sources, sinks, and isotopic fractionation of antimony in a karst catchment: constraints on multi-media migration and biogeochemical cycling - Yu Lin; Guangyi Sun; Xinyu Li; Yunjie Wu; Yu Cheng; Heng Yao; Xinbin Feng (Geochimica et Cosmochimica Acta, 2026)

16S rDNA sequencing combined with non-targeted metabolomics profiling reveals the mechanism of simulated digestion ultra-sound pea protein isolate in vitro - Xinyu Zhao; Xuemei Dong; Jianke Fang; Chun Li; Lin Zhao; Guofang Zhang; Peng Du; Tong Zhang; Xinyao Sun; Libo Liu; Wenkui Guo (Food Bioscience, 2026)

Selenium regulates pyroptosis through the ROS-mtDNA-cGAS-STING axis to alleviate trimethyltin chloride-induced inflammation in chicken kidneys - Huiling Zheng; Xinyu Huo; Wenwen Zhang; Shuang Lou; Mingyue Li; Chenxi Huang; Kang Yang; Tong Xu; Hongjin Lin (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Interplay between convection and wind in driving surface mixing in the Xiangjiaba Reservoir, China - Lidi Shi; Jian Sun; Xinyu Zuo; Khosro Morovati; Carlo Gualtieri; Binliang Lin (Hydrological Sciences Journal, 2026)

Benzyl isothiocyanate inhibits the conjugative transfer of mcr-1-positive plasmid via suppressing intercellular contact and limiting energy supply - Ping Cheng; Shuying Liang; Shixin Gui; Xinyu Wang; Lingfeng Yu; Wenjun Cui; Chunxu Lu; Lin Li (Journal of Environmental Management, 2026)

Octenylsuccinic acid modification promotes starch lecithin complexation: Application to the preparation of oleogels - Xinyu Wang; Qian Lin; Li Niu; Wenqing Zhao; Qi Zhao; Ruijie Li; Wenhao Li (Food Hydrocolloids, 2026)

Oxygen vacancy engineered M0.5Ni0.5Fe2O4 for enhanced chemical looping combustion performance - Xinyu Li; Jianshuai Li; Lina Wang; Lei Liu; Yan Lin; Shenglong Teng; Yiwen Song; Dewang Zeng; Yu Qiu (Chemical Engineering Journal, 2026)

Gas-synergistic ferroptosis of tumor cells to activate Mg-mediated immunotherapy - Fanchao Que; Qingdeng Fan; Haobin Cai; Tianshui Bai; Lin Huang; Zehui Wang; Haolong Ma; Xinyu Chen; Bin Ren; Jing Yang; Chunmei Chen; Zhiqin Deng; et al. (Chemical Engineering Journal, 2026)

Epidemiological characteristics of Chlamydial infection in hospitalized children in China: A nationwide retrospective study - Huiwen Zheng; Xinyu Wang; Xirong Wu; Yajie Guo; Feina Li; Jing Xiao; Hui Qi; Weiwei Jiao; Guoshuang Feng; Ju Yin; Lin Sun (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

The role of KPNA3 in multiple myeloma: implications for targeting nuclear import - Hongmei Luo; Ziyue Mi; Jingcao Huang; Jingjing Wen; Siyao He; Haonan Yang; Yue Zhang; Linfeng Li; Xiang Liu; Xinyu Zhai; Fangfang Wang; Xinai Gan; et al. (Apoptosis, 2026)

Photo-responsive polyprodrug supramolecular assemblies with self-accelerated subcellular delivery for synergistic photochemotherapy - Ming Liu; Zhenduo Zhao; Ming Li; Yitian Chen; Yicheng Wang; Xuehua Lin; Xinyu Wang; Qinghao Zhou; Zhishen Ge; Yongan Tang; Yibin Deng; Yuliang Zhao; et al. (Science Bulletin, 2026)

Solid phase iron-driven Feammox for continuous flow low carbon to nitrogen ratio wastewater: The dual role of functional bacteria recruitment and community coordination optimization - Chisheng Yu; Qiang Lin; Liang Zhu; Ancheng Luo; Xinyu Chen; Kaiying Chen; Tianyu Xu; Zhiwei Liang (Journal of Environmental Chemical Engineering, 2026)

Engineering advanced composites of transition metal hexacyanoferrates for enhanced cesium ion capture: A review on design strategies and performance - Xinyu Liu; Zonglin Pan; Ruisong Xu; Lin Li; Shuaifei Zhao; Chengwen Song; Tonghua Wang (Journal of Environmental Management, 2026)

Unlocking the potential of umami peptides: A comprehensive review of preparation methods, evaluation strategies, health benefits, and taste transduction mechanisms - Jianhua Zhao; Xinyu Li; Lunjie Huang; Hongbin Lin; Qiang He (Food Research International, 2026)

A novel strategy for controlling nitrite accumulation in fermented cabbage by regulating microbial community structure via cold plasma - Lin Zhu; Mengke Cheng; Yuan Wang; Xinyu Hu; Rong Wang; Biyue Yang; Xiang Xiao; Wei Wei (Food Control, 2026)

Benzo[c]chromene-based light-emitting conjugated polymer for high performance deep-blue PLEDs - Hong Ren; Zhiyang Sun; Xiang An; Qian Wu; Xinyu Du; Xiaoqi Guo; Wenyu Chen; Mengyuan Li; Jiabin Liu; Dunliang He; Ning Sun; Lubing Bai; et al. (Chemical Engineering Journal, 2026)

Fine-tuned Ce electron density directs H2O2 activation pathway in industrially employable CeO2 nanozymes for ∼100% specificity and boosted activity in (Bromo)peroxidase mimicking - Tianqi Cheng; Bo Yuan; Chao Zhao; Zicong Tan; Xinyu Wu; Jian Lin Chen; Juan Liu; Yufei Zhao; Hui Wei; Yung-Kang Peng (Chemical Engineering Journal, 2026)

Engineering local donor-acceptor architecture in a porphyrin-based metal-organic framework for enhanced sonocatalytic immunotherapy - Yarui Hu; Sainan Liu; Jiwei Wang; Zhendong Liu; Xinyu Ma; Junhao Shao; Binbin Ding; Ping'an Ma; Jun Lin (Chemical Engineering Journal, 2026)

Mesoporous catechin nanocarriers potentiate curcumin to treat osteoarthritis via synergistic antioxidant and macrophage repolarization - Xinyu Zhang; Junyan Li; Ye Zhu; Huilin Hu; Ping Gong; Hui Xu; Ningli Guo; Quanzhou Wu; Chao Lou; Minghao Chao; Zhang Chen; Minjiang Chen; et al. (Chemical Engineering Journal, 2026)

Bias correction of subseasonal to seasonal precipitation forecasts over the Tibetan Plateau based on CMA climate prediction models - Xinyu Chen; Minhong Song; Ziqiang Zhou; Yaqi Wang; Tongwen Wu; Zhiqiang Lin (Atmospheric Research, 2026)

Ball Milling-Assisted Fabrication of Zirconium-Biochar-Zeolite Composites for Phosphate Removal in Aquatic Systems - Xiao Ling; Xinyu Qi; Wenshan Peng; Yapeng Liu; Cunguo Lin; Haiying Guo; Xiaoheng Geng (Water, Air, & Soil Pollution, 2026)

CSSL-based GWAS identifies SNPs and candidate genes associated with Verticillium wilt resistance in cotton - Youzhong Li; Xiaohui Jiang; Hongyu Cao; Xinyu Zhang; Zhongxu Lin; Qian-Hao Zhu; Yanjun Li; Fei Xue; Shuaishuai Cheng; Feng Liu; Jie Sun (Theoretical and Applied Genetics, 2026)

A synthetic biocontrol consortium of Streptomyces salinarius and Bacillus halotolerans exhibits superior protection against Fusarium oxysporum infection in Pinus via synergistic interactions - Haixia Wang; Lin Fu; Chunli Li; Xuanyi Meng; Siyang Wang; Xinlu Zhang; Xinyu Zhou; Xiangna Wang; Fangliang Zheng; Chunyu Zhu (Plant and Soil, 2026)

Descent-rate-adaptive salinity correction for underway conductivity-temperature-depth profiler data - Xuan Wang; Zhigang Chen; Lin Cao; Shousheng Liu; Yang Zhou; Xu Chai; Jiliang Ding; Fei Wu; Fengxiang Guo; Xinyu Li; Zhigang Gai (Acta Oceanologica Sinica, 2026)

Onset and decay mechanisms of the Summer 2024 extreme marine heatwave in the Taiwan Strait - Ruizhao Xia; Yun Qiu; Xinyu Lin; Shihan Li (Acta Oceanologica Sinica, 2026)

Disparities in bioaccumulation of chlorinated organic pollutants in O. bartramii and seawater from the Northwest Pacific Ocean: Compound – specific mechanisms and health risks - Ci Wang; Xinran Liu; Yitong Gao; Zilan Wu; Li Zhang; Jingqian Xie; Xinyu Tian; Feng Wu; Xiaojie Dai; Bilin Liu; Tian Lin (Marine Pollution Bulletin, 2026)

Organophosphate esters (OPEs) in a marine food web of the Yellow Sea, China: Bioaccumulation, trophodynamics, and model prediction - Baolin Liu; Xinyu Ma; Xiaosheng Lin; Junjie Li; Sixu Liu; Weihua Dong; Yong Yu (Marine Pollution Bulletin, 2026)

Effects of mixed microalgae on larval metamorphosis of the Pacific white shrimp Penaeus vannamei: Integrated analysis of digestion, antioxidant capacity and transcriptome - Yiting Wu; Yujia Zhai; Xinyu Li; Shengwei Lin; Zhihao Zhang; Xinchen Wang; Fenglu Han; Chang Xu; Erchao Li (Aquaculture, 2026)

Microbial mechanisms underlying differences of methane emissions between urban and rural wetlands - Yuwen Lin; Xinyu Yi; Chen Ning; Yong Li; Yinghe Peng; Shuguang Liu; Changhui Peng; Xiaoyong Chen; Shuailong Feng; Pengpeng Duan; Yan Liu; Juyang Liao (Soil Biology and Biochemistry, 2026)

Comparison of metabolomic and transcriptomic analyses of Ganping mandarin fruit following on tree storage and postharvest low temperature storage - Xinyu Huang; Luoao Lin; John B. Golding; Penta Pristijono; Su Guo; Youjian Yu; Gang Chen; Dongdao Han; Huqing Yang; Ruihua Bai; Yongxin Li (Postharvest Biology and Technology, 2026)

Ketamine's brain spatial distribution and metabolic effects in a mouse model of anxiety: Insight into in situ mass spectrometry imaging and metabolomics methods - Hong Yang; Weihao Fan; Xinyu Yang; Ying Wei; Li Xiao; Hongkun Yang; Linzhi Jiang; Jian Li; Kaiting Shi; Shuang Zhao; Lin Yang; Yi Ye; et al. (NeuroToxicology, 2026)

Unveiling the degradation behavior of naproxen in an enhanced UV222 advanced oxidation system: Mechanisms, efficiency gains, and actual water applicability - Xinyu Wang; Baozhen Liu; Shaoxia Lin; Zhenqi Du; Zhikang Wang; Xinyue Zhao; Ruibao Jia; Yonglei Wang (Journal of Environmental Management, 2026)

Radioactivity of 14C, OBT, and TFWT in seafood from coastal areas of Zhejiang Province: Assessment of internal exposure to the public - Hong Ren; Kaiwen Tan; Feng Lin; Taotao Zheng; Xiaoxiang Ma; Peng Wang; Shunfei Yu; Hua Zou; Xinyu Gong; Yiyao Cao (Food Control, 2026)

Water-heat separation evaporator design for efficient solar steam generation utilizing thermal radiation-convection hybrid mechanism - Jinbu Su; Weixin Du; Yunong Xie; Xuli Lin; Chenyi Shi; Xinyu Dong; Yuyi Xu; Jing Shi; Chengbing Wang (Desalination, 2026)

Tectonic influence on the characteristics of contourite systems - Zhi Lin Ng; Shan Liu; Hui Chen; Shaoru Yin; F. Javier Hernández-Molina; Débora F.P. Duarte; Xinyu Xue; Zhixuan Lin; Kunwen Luo; Ming Su (Earth-Science Reviews, 2026)

Hydrophobic association-reinforced polymerizable deep eutectic ionic gels for next-generation wearable electronics: Multilevel dynamic network construction and multifunctional integration - Qiuyan Luo; Jia Jiang; Yuhang Lin; Hucheng Fu; Zewen Wu; Meng Wang; Yiting Xu; Xinyu Liu; Birong Zeng; Lizong Dai (Chemical Engineering Journal, 2026)

Functional characterization of PsnErf1b in regulating salt stress tolerance in poplar - Zihan Cheng; Xinyu He; Xinyue Tu; Haiyan Fang; Lin Liu; Tingbo Jiang; Xuemei Zhang (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

A smartphone-assisted dual-mode sensor for synchronous detection of Microcystin-LR in environmental water via Temperature–Multicolour dual signals - Hongjian Lin; Yiwen Zhu; Xiaoya Chen; Huilian Sun; Xinyu Cao; Mengyu Tao; Jingqi Zhou; Hong Huang; Bingyong Lin; Longhua Guo (Analytica Chimica Acta, 2026)

The formation of autophagosomes in the development process of rice endosperm is affected by endogenous ascorbic acid - Le Yu; Mengwei Chen; Haoran Yan; Zeliang Ouyang; Xinyu Liu; Sitong Lin; Yixuan Tang; Zhipeng Xu; Chunyu Liu; Peiyi Chen; Liping Zhou; Yonghai Liu (Acta Physiologiae Plantarum, 2026)

Tracking mitigation and expression patterns of the antibiotic resistome during full-scale livestock wastewater treatment: Comparison between summer and winter conditions - Xinyu Zhu; Limin Lin; Feng Ju (Water Research, 2025)

Investigating the application of 3D skin models in micronucleus assay and comet assay - Tianyin Lin; Huan Luo; Jingqiu Sun; Chen Dong; Xinyu Hong; Ping Xiao; Gonghua Tao (Toxicology Letters, 2025)

Toxicological effects of diquat on the central nervous system and associated treatment challenges - Xinyu Wang; Yunxia Liu; Meng Yang; Yunwen Wang; Feng Guo; Lin Wang (NeuroToxicology, 2025)

Enhanced photothermal combustion efficiency of propane in the presence of SO2 over Mo-doped Pt/WO3 catalyst: Rational utilization of Ptδ+-(SO4)δ- - Lijing Han; Huimin Chai; Jinliang Lin; Kaiting Chen; Qingwei Li; Qiuhong Zhou; Jun Ye; Hai Liu; Xinyu Han; Zeshu Zhang; Yibo Zhang (Journal of Environmental Chemical Engineering, 2025)

Transcriptomic investigation reveals a potential mechanism of white LED irradiation inhibiting the growth and pathogenicity of the blue mold pathogen Penicillium expansum - Yiliang Cai; Jingjing Shan; Xinyu Mao; Zihan Zhang; Wei Hong; Weilun Wang; Chao Zhao; Haiyan Lin; Ruiyu Zhu (Food Microbiology, 2025)

Spotted knifejaw (Oplegnathus punctatus) TARBP2 negatively regulates type I IFN responses to promote RGNNV replication - Yijie Lin; Weifu Mo; Xinyu Liao; Minyao Bi; Siting Wu; Qiwei Qin; Jingguang Wei (Fish & Shellfish Immunology, 2025)

Machine learning applications in tight porous media: Challenges, advances, and future directions - Guiang Li; Chengyan Lin; Yuqi Wu; Pengjie Ma; Pejman Tahmasebi; Chunmei Dong; Weibin Liu; Xinyu Du; Ziru Zhao (Earth-Science Reviews, 2025)

Stepwise mechanochemical ball milling induced lattice destruction‑oxygen vacancy regulation promotes large-scale lithium leaching from spent lithium-ion battery cathodes - Jian Wang; Xingsheng Li; Zhikui Zhou; Yanyan Xia; Xinyu Liu; Zixiang Lin; Guanhua Jin; Xiaoyun Fan (Chemical Engineering Journal, 2025)

BreathFIT: Liquid metal-PDMS sticky conductors and AuNPs/MXene biosensors for synchronous EMG-lactate monitoring in respiratory health - Yang Liu; Zixin Lin; Yuetao Zhang; Xinyu Zhang; Zhiqi Li; Rubing Xiong; Chunxiao Long; Jiaqi Huang; Can Liu; Ziwei Zheng; Dan Li; Yongchang Ouyang; et al. (Chemical Engineering Journal, 2025)

In-situ polymerized ether-ester copolymer electrolytes with regulated solvation structure for quasi-solid-state lithium metal batteries - Guocheng Wang; Yongjie Dan; Xinyu Lin; Qi Liu; Yanhua Niu; Guangxian Li (Chemical Engineering Journal, 2025)

Fe/Mn/Zr ternary electrode facilitates ultra-low-resistance electrocatalysis for closed-loop electrochemical removal of heavy metals from industrial wastewater - Shaoying Lin; Xinyu Liu; Huiqiang Ma; Yanzhuang Liu; Yameng Wang; Haoran Liu; Bo Wang; Yihua Li; Changfei Gao (Chemical Engineering Journal, 2025)

Cobalt-doped sunflower plate-derived porous carbon as a dual-functional cathode host for high-performance Li S batteries via synergistic confinement-catalysis - Ying Fang; Bin Yue; Lin Li; Yuqi Wang; Xinyu Yan; Jinxian Wang; Yang Su; Guixia Liu; Wensheng Yu; Xiangting Dong (Chemical Engineering Journal, 2025)

Schiff base-grafted bacterial cellulose-PCL composites: Humidity/temperature-driven hydrogen bond reconfiguration for mechanically adaptive nanofiber - Chenchen Qin; Bianjing Sun; Xinyu Chen; Du Ping; Wuxin Bai; Lin Shi; Ahsan Nazir; Chuntao Chen; Dongping Sun (Chemical Engineering Journal, 2025)

Statistical inferences of differences and correlations in the seismic frequencies of large-scale fault zones in Western Sichuan, China - Yuan Xue; Dan Hu; Junreng Ge; Xinyu Yao; Mingyue Dai; Bingyan Fan; Yu Ming; Muchen Lin (Journal of Seismology, 2025)

Non-coding RNAs-regulated SLC7A11 modulates ferroptosis: a new strategy for cancer therapy - Xinyu Niu; Jiawen Nie; Lijie Zhang; Feng Chen; Zhijuan Lin (Functional & Integrative Genomics, 2025)

Transcription factor MAZ activates the transcription of hypomethylated TYMP in ccRCC - Yihan Dong; Xinyu Liu; Jiaxin Li; Tianyu Lin; Rui Wang; Huamao Jiang; Yong Wang; Dan Yue (Functional & Integrative Genomics, 2025)

Modulation of growth, gut-liver axis, and antioxidant defense by Bacillus tequilensis (GCB-3) in grass carp (Ctenopharyngodon idella) under high-carbohydrate diet: Insights into health enhancement and oxidative stress mitigation - Xin Wang; Dongming Zhang; Xinping Zhang; Xinyu Lei; Dan Jiang; Lili Lin; Wenli Zhu; Sibu Wang; Quan Huang; Yuxin Li; Yu-ke Chen; Zhixin Guo (Animal Feed Science and Technology, 2025)

Underwater sea cucumber detection based on domain-invariant features - Fangqun Niu; Zejin Liu; Xinyu Zheng; Junyi Wang; Dexuan Zhang; Yuanshan Lin; Xiaoting Zhu; Shuai Yang; Wei Wang; Guodong Li (Aquaculture International, 2025)

Effects of miR-200b-3p and miR-424–5p regulating notch signaling pathway on atherosclerosis induced by PM2.5 in vitro - Tianyang Zhao; Xu Li; Zhili Ge; Jingjing Shi; Tianyou Wang; Jiaxin Zhang; Xinyu Zhang; Huibin Jiang; Liting Zhou; Lin Ye (Toxicology, 2025)

Feature evaluation, regression prediction and scenario analysis of carbon emissions from city building operations: Evidence from 362 Chinese cities - Xinghui Zhang; Qi Wang; Xinyu Jia; Yang Zhao; Hao Zhou; Borong Lin; Cong Zhang (Sustainable Cities and Society, 2025)

Application of a thiophene-based conjugated polymer in the photocatalytic eradication of multidrug-resistant bacteria: Synergistic inactivation of MRSA via carboxyl capture and multi-pathway regulation - Ying Xu; Simiao Wang; Xinyu Yu; Yuncong Wang; Lin Han; Yu Wang; Haiyong Guo; Juan Du (Journal of Hazardous Materials, 2025)

A new framework integrating crop growth–level IV fugacity model and eco-indicator sensitivity to assess neonicotinoid fate and ecological risk in tropical rice–vegetable rotations - Huadong Tan; Xinyu Hu; Linxia Zhang; Yiru Chen; Rong Hao; Zhenzhen Wang; Chunyuan Wu; Xiaoying Zhang; Xiao Deng; Yi Li; Lin Wu; Yi Zhang (Journal of Hazardous Materials, 2025)

In-situ growth of TiO2 nanoparticles on MXene to construct 3D copper-based catalyst for methanol steam reforming - Rensheng Song; Guangbo Zhou; Minghui Lian; Haodong Chen; Lei Wang; Jinxiao Li; Chunhua Yang; Xinyu Lin; Liwei Pan (Fuel, 2025)

Experimental study and constitutive model for the bond behavior of corroded H-shaped steel in concrete - Yongjun Lin; Liwen Sun; Sihua Jiang; Jie Zhou; Xinyu Liu (Engineering Structures, 2025)

Machine learning-enhanced microfluidic CircRNA detection platform for high-accuracy breast cancer diagnosis - Xinyu Zhang; Zixin Lin; Huanyu Zhou; Qitao Xie; Yuetao Zhang; Yongmei Chen; Zijie Li; Runlin Lv; Zhiqi Li; Rubing Xiong; Xiaman Chen; Yong Xia; et al. (Chemical Engineering Journal, 2025)

Cobalt-embedded carbon nanotube-bridged hollow carbon cubes enabling electron/ion co-transport and catalytic conversion in lithium-sulfur batteries - Xinyu Yan; Bin Yue; Lin Li; Yuqi Wang; Ying Fang; Ye Li; Yang Su; Jinxian Wang; Wensheng Yu; Xiangting Dong (Chemical Engineering Journal, 2025)

Bayesian-assisted mechanochemical synthesis of carboxylated cellulose nanocrystals and its application in Pickering emulsion - Xinyu Lin; Weike Su; Qihong Zhang (Carbohydrate Polymers, 2025)

LINC02266 promotes proliferation and metastasis and inhibits ferroptosis of gastric cancer cells by regulating AKT/ACSL4 pathway - Xiaoru Liang; Xinyu Niu; Lijie Zhang; Chang Liu; Xiaomin Zhao; Feng Chen; Zhijuan Lin (Molecular and Cellular Biochemistry, 2025)

A SERS-active microneedle array for rapid and minimally invasive lactic acid detection - Xinyu Sun; Kequan Chen; Yang Wang; Zhiwei Zhang; Jinfeng Lin; Guiling Liu; Dianhuai Meng; Jian Dong; Yan Huang (Analytica Chimica Acta, 2025)

GM-CSF-adjuvanted Newcastle disease virus-vectored bivalent vaccine elicits enhanced dual immunity against Newcastle disease and infectious bursal disease in chickens - Qing Wu; Jinmiao Liu; Weiyue Cao; Jiaxin Li; Huimin Li; Yuhan Jin; Zhitong Li; Xinyu Li; Wenying Sun; Lin Bai; Xinyuan Shen; Xiaochen Guo; et al. (Veterinary Immunology and Immunopathology, 2025)

The role of endoplasmic reticulum stress in Atrazine-induced hepatic lipid accumulation - Honghao Qian; Shuping Ren; Haotang Zhao; Jingjing Shi; Zhili Ge; Jiaxin Zhang; Tianyou Wang; Xinyu Zhang; Huibin Jiang; Yuezhu Zhang; Lin Ye (Toxicology Letters, 2025)

Near-surface turbulence mixing in a large channel-type reservoir: Potential impacts on phytoplankton distribution - Lidi Shi; Jian Sun; Mathew Wells; Khosro Morovati; Carlo Gualtieri; Maozhou Wu; Xinlu Wang; Binliang Lin; Xinyu Zuo (Journal of Hydrology, 2025)

Assessment of environmental and health impacts during 3D printing of candidate polymeric materials for space additive manufacturing - Junling Li; Yi Liu; Chao Peng; Qifan Liu; Wei Zhao; Mingyuan Liu; Xinyu Du; Yongyin Yan; Yufei Song; Kaihui Xia; Chun Chen; Haijie Zhang; et al. (Journal of Hazardous Materials, 2025)

Catalytic upgrading of clean biogas to synthesis gas via bi-reforming over bimetallic NiCo catalysts - Xinyu Huang; Weiting Lin; Zhichao Zhao; Pengyin Lu; Jun Xie; Jiawei Zhong; Yong Chen (Journal of Environmental Chemical Engineering, 2025)

Pig bedding biochar enhances the Cd extraction capacity of Perilla frutescens by mitigating the toxicity of Cd-contaminated soil - Tianlian He; Xingyu Hao; Rui Jing; Zhenguo Li; Ying Chen; Mingwei Yang; Chengzhen Gu; Yulin Wang; Ruiyu Lin; Xinyu Zheng (Journal of Environmental Sciences, 2025)

The antibacterial activity and metabolomic analysis of the recombinant lectin protein PFL-96 derived from Pinctada fucata against Streptococcus agalactiae isolated from tilapia (Oreochromis niloticus) - Xiaojian Mo; Wenyue Li; Jianbing Liu; Qiting Li; Zhongxiu Liang; Xinyu Liang; Jiaxing Tang; Jiahui Liang; Jiang Lin; Peng Liu (Fish & Shellfish Immunology, 2025)

Ground subsidence monitoring and prediction based on InSAR and CNN-BiGRU-Attention: A case study of Chengdu - Zhihua Zhang; Qiang Lin; Haowen Yan; Xinyu Zhu; Xinxiu Zhang; Shuwen Yang; Chunlin Huang; Yueling Shi; Jie Hu; Xuhui Li; Li Hou; Lujia Zhao; et al. (Engineering Geology, 2025)

From ultrafiltration to nanofiltration: structural engineering of polyetherketone membranes via additive-assisted thermal crosslinking for superior organic solvent resistance - Xiangmin Xu; Yuefei Rong; Mengjie Hou; Meudjeu Tognia; Xinyu Dong; Lin Li; Tonghua Wang (Chemical Engineering Journal, 2025)

Self-amplifying cuprophoric nanocatalyst reprograms mitochondrial copper homeostasis to drive tumor-selective cuproptosis in oral squamous cell carcinoma - Xinyu Liu; Ying Zhang; Chen Mao; Xin Jin; Jing Yang; Zhichao Xiao; Lin Huang; Zhenxiong Zhao; Fusen Peng (Chemical Engineering Journal, 2025)

CuO/M(OH)₂ (M = Mg, Ca) heterostructures with in-situ oxygen vacancies enable room-temperature ultrahigh triethylamine sensing - Ruixiang Li; Shu Chen; Beibei Wang; Xiaodan Wang; Xinyu Hu; Sonia Estrade Albiol; Cristian Fabrega Gallego; Hao Shen; Chunhua Luo; Hui Peng; Hechun Lin (Chemical Engineering Journal, 2025)

Disulfide bond enhanced piezocatalytic self-Fenton process in MoS3 for singlet oxygen dominated organic pollutant degradation with cytotoxicity assessment products - Xinyu Xu; Wenzhi Du; Rumeng Yang; Tianjian Zhao; Lin Tao; Yichao Huang; Yuanyi Zhou; Jiayue Hu; Mingshan Zhu (Chemical Engineering Journal, 2025)

Salinity-independent evaporation: Biomimetic design of large hydrogel evaporator with 3D hierarchical channels in high-salinity brine - Jinbu Su; Xuli Lin; Chenyi Shi; Xinyu Dong; Jinchi Ma; Yunong Xie; Yuyi Xu; Weixin Du; Chengbing Wang (Chemical Engineering Journal, 2025)

Engineering a recombinant VP2-Based neutralizing epitope vaccine candidate against canine parvovirus: a preliminary immunogenicity assessment - Qing Wu; Yuhan Jin; Weiyue Cao; Zeheng Ren; Xinyu Li; Zhitong Li; Jiachi Han; Chunxu Shi; Rui Gao; Min Yan; Shengrui Zhu; Wenpeng Guan; et al. (Veterinary Research Communications, 2025)

Natural product-based nanotechnological formulations for colorectal cancer treatment - Lanfang Wu; Jiali Wu; Xinyu Wang; Youfa Xu; Zhizhe Lin; Jianming Chen; Xin Wu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Domain generalization for sea cucumber detection: Tackling background color variability in aquaculture settings - Fangqun Niu; Yifan Sheng; Junyi Wang; Xinyu Zheng; Kexin Liu; Yuanshan Lin; Wei Wang; GuoDong Li (Aquaculture International, 2025)

Design of a Wearable Finger PPG-Based Blood Glucose Monitor - Mutian Wang; Xuelei Liu; Wenyi Han; Xinyu Lin; Xin Chen; Shun Zhao; Zhiqiang Zhuang; Leian Zhang; Peiqiang Su (Annals of Biomedical Engineering, 2025)

Evaluating the therapeutic qualities of community parks: An elderly-centric perspective - Xinyu Lin; Wardah Fatimah Mohammad Yusoff; Mohd Khairul Azhar Mat Sulaiman (Urban Forestry & Urban Greening, 2025)

3-hydroxykynurenine increase in kynurenine pathway driven bisphenol F induced anxiety- and depression-like behaviors - Yuxin Lin; Luyao Wang; Sining Meng; Jianjia Liu; Xinyu Li; Wenjuan Wang; Miaoyang Hu; Xi Wang; Weixia Duan; Shangcheng Xu; Jun Wang; Rong Gao (Science of The Total Environment, 2025)

Deciphering the nexus of soluble microbial products (SMPs) and membrane fouling: Roles, mechanisms, and control strategies - Xinyu Hu; Hongjun Lin; Genying Yu; Liguo Shen; Jiaheng Teng; Meijia Zhang; Bisheng Li; Leihong Zhao; Die ling Zhao; Cheng Chen (Chemical Engineering Journal, 2025)

Percolating dynamic ion-conduction network in composite polymer electrolyte for high-performance lithium metal batteries - Xueying Yang; Chenxi Sun; Ruiyang Li; Nanbiao Pei; Xinyu Li; Yi Deng; Peng Zhang; Jie Lin; Jinbao Zhao (Chemical Engineering Journal, 2025)

Amino-enhanced MIL-101(Fe) piezocatalysis for in-situ hydrogen peroxide generation and selective production of 1O2 for organic pollutants degradation - Wenzhi Du; Xinyu Xu; Rumeng Yang; Yuxing Qiao; Yingying Yu; Lin Tao; Jiayue Hu; Yichao Huang; Mingshan Zhu (Chemical Engineering Journal, 2025)

Genome-Wide Identification and Expression Analysis of the Basic Helix-Loop-Helix (bHLH) Transcription Factor Family in Gastrodia elata - Shanshan Lan; Xin Lin; Maoqiong Wei; Guangheng Feng; Hongcheng Liu; Jinliang Shao; Xinyu Li; Zeli Chen; Zhenhuan Liu (Plant Molecular Biology Reporter, 2025)

Thermal processing of Oilseeds: Multidimensional impacts on Maillard reaction chemistry, nutritional safety, and technological innovations in quality control - Xinyu Li; Xinyue Liu; Zhiqiang Kong; Lin Li; Long Li; Marie-Laure Fauconnier; Minmin Li (Trends in Food Science & Technology, 2025)

Identification of the sources and migration of antimony in karst terraces via Sb stable isotopes - Yunjie Wu; Guangyi Sun; Yu Lin; Xinyu Li; Yu Cheng; Heng Yao; Xinbin Feng (Journal of Hazardous Materials, 2025)

Insight into the enhancement mechanism of repeated freezing-thawing pretreatment promotes carboxymethylation for improving the properties of sweet potato starch: From a multiscale structural perspective - Li Niu; Siwen Yu; Xinyi He; Wei Liang; Qian Lin; Qi Zhao; Xinyu Wang; Ruijie Li; Wenhao Li (Food Chemistry, 2025)

PTPN2 modulates antiviral immunity in grouper by promoting TBK1 degradation and suppressing interferon signaling - Xinyu Liao; Yijie Lin; Weifu Mo; Siting Wu; Qiwei Qin; Jingguang Wei (Fish & Shellfish Immunology, 2025)

An Ethylicin Dosage Form - for Bacterial Wilt Disease Control - Lei Yang; Dong Xiang; Guan Lin; Zhihao Gao; Xinyu Hu; Juntao Gao; Yong Liu (Journal of Plant Biology, 2025)

Dual-channel mechanism of groove music fused with Tai Chi to improve cognitive-emotional abilities in older adults based on a coupled fNIRS-EMG analysis: a randomized controlled study - Haojie Li; Xinyu Lin; Xie Wu (GeroScience, 2025)

A biomimetic liposome platform targeting non-small cell lung cancer to modulate the inflammatory and metabolic microenvironment for enhanced therapy - Xinyu Jiang; Pengfei Mao; Minghui Wang; Dingchao Shen; Linyi Zhang; Yingyi Zhao; Xindan Liang; Zihao Huang; Yunzhi Wang; Yinhao Lin; Zihao Tao; Yuqi Han; et al. (Chemical Engineering Journal, 2025)

Synergistic effect of canine FGF-21 combined with insulin in the treatment of canine diabetes - Wenying Sun; Yaoqun Wang; Ziran Liu; Qing Wu; Xiaochen Guo; Zhitong Li; Xinyu Li; Chunxu Shi; Rui Gao; Lin Bai; Jingming Wang; Yuhan Zhang; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Nanocomplex of selachyl alcohol and sodium caseinate: Preparation, physicochemical properties, and interaction mechanism - Junbo He; Xinyu Zhang; Yijie Li; Hong Lin; Weinong Zhang (Food Chemistry, 2025)

Formation of aroma characteristics driven by microorganisms during long-term storage of Liubao tea - Chang Xu; Jinming Zhang; Yani Pan; Xinyu Feng; Anran Yan; Xinxin Wang; Lin Xiang; Haowei Guo; Lixin He; Tianyuan Chen; Fangyuan Fan; Shuying Gong; et al. (Food Chemistry, 2025)

Insights into Leuconostoc-clade as starters in Chinese paocai: Shaping microbial communities for rapid, safe, and flavor-preserving fermentation - Xinyu Hu; Mengke Cheng; Meng Zhang; Biyue Yang; Rong Wang; Juan Bai; Jiayan Zhang; Wei Wei; Lin Zhu; Xiang Xiao (Food Bioscience, 2025)

RNA chaperone Hfq promotes the growth of Yersinia enterocolitica in refrigerated foods - Ming Liu; Xinyu Zhao; Zhi Wang; Ling Chen; Zimeng Wang; Huichan Zhai; Congyu Zhou; Huixian Wang; Yu Ding; Jumei Zhang; Xiuhua Lin; Jiahui Zeng; et al. (Food Microbiology, 2025)

Enhancing oil/water emulsion separation with inkjet printed beetle-inspired zeolitic imidazolate framework-67 modified membranes - Xinyu Hu; Hongli Xie; Hao Wang; Liguo Shen; Renjie Li; Hongjun Lin; Leihong Zhao; Genying Yu (Desalination, 2025)

Computational design and efficacy assessment of Bufalin-Dendrimer nanoformulation for enhanced cancer therapy - Yurong Sun; Yinhua Lin; Huaitao Sun; Junfa Yang; Hui Cheng; Jia Yi; Wenqiang Li; Gen Lu; Cheng Zhao; Yuge Jiang; Xinyu Zhao; Qinglin Li; et al. (Chemical Engineering Journal, 2025)

Impact of flow configuration on microbial ecological processes and health risks in biological activated carbon filters - Zedong Lu; Yazhou Sun; Xing Li; Yuhao Xie; Xinyu Lin; Jiawei Ren; Zhiwei Zhou (Chemical Engineering Journal, 2025)

Boosting the selective hydrogenation of renewable unsaturated aldehydes to alcohols over CeO2 with different morphology - Zhendong Yu; Hongyuan Liu; Renjie Huang; Binglin Chen; Zheng Li; Xinyu Huang; Hua Zhang; Aiyong He; Lu Lin; Xianhai Zeng (Chemical Engineering Journal, 2025)

PSAT1 promotes the progression of colorectal cancer by regulating Hippo-YAP/TAZ-ID1 axis via AMOT - Minshan Tang; Kai Song; Danning Xie; Xinyu Yuan; Yaxuan Wang; Zhiyang Li; Xiansheng Lu; Liang Guo; Xiaotong Zhu; Le Xiong; Wenqian Zhou; Jie Lin (Molecular and Cellular Biochemistry, 2025)

Rational design and pairing of single-domain antibodies for developing rapid detection methods for botulinum neurotoxins A and B - Ruomei Lv; Jiaxin Li; Xinyu Fang; Li Tang; Rui Shi; Jin Wang; Wenjing Zhang; Jinglin Wang; Guangyu Zhao; Jing Wang; Shan Gao; Xuefang Xu; et al. (Analytica Chimica Acta, 2025)

Does collaborative governance of natural disasters in urban agglomerations enhance urban resilience? Evidence from China - Lianlong Ma; Dong Huang; Xinyu Jiang; Lijiao Yang; Maomao Zhang; Yue Lin (Environment, Development and Sustainability, 2025)

Efficient removal of tetracycline under neutral pH using FeOCl-modified carbon-based catalytic membrane via in-situ coupling fenton oxidation - Zonglin Pan; Xinyuan Zhou; Xinyu Liu; Chengwen Song; Wei Qian; Hang Yu; Ruisong Xu; Lin Li; Shuaifei Zhao; Tonghua Wang (Journal of Water Process Engineering, 2025)

Catalytic upgrading of biogas exclusively to metgas (CO-2H2) through the combined steam and dry reforming over Sm2O3 promoted robust Ni nano-catalysts supported on boron nitride nanosheets - Xinyu Huang; Weiting Lin; Pengyin Lu; Zhichao Zhao; Jiawei Zhong; Jun Xie; Yong Chen (Fuel, 2025)

Altered 3D genome reorganization mediates precocious myeloid differentiation of aged hematopoietic stem cells in inflammation - Xinyu Cui; Yu Dong; Qiang Zhan; Yixin Huang; Qianshu Zhu; Zihao Zhang; Guang Yang; Liping Wang; Shijun Shen; Jia Zhao; Zhiyi Lin; Jiatong Sun; et al. (Science China Life Sciences, 2025)

Rapid electrothermal upcycling hexachlorobutadiene (HCBD) polluted distillation residue into turbostratic graphene for enhanced electromagnetic wave absorption - Tong Chen; Yunxiao Zhao; Hanyang Sun; Xinyu Niu; Pei Li; Yan Xia; Xiaoqing Lin; Xiaodong Li; Ying Wang; Jianhua Yan; Chen Sun (Journal of Hazardous Materials, 2025)

An organic cage-based adsorbent for removing triphenylmethane dyes based on charge-assisted hydrogen bonding - Lei Zhang; Jiabin Lu; Qi Liu; Yongsheng Guo; Lin Sun; Ruiyu Jiang; Xinyu Song (Journal of Environmental Chemical Engineering, 2025)

Natural borneol improves cellular uptake of curcumin to enhance its photodynamic bactericidal activity against Escherichia coli ATCC 8739 - Zhenlong Zhou; Ruoxin Chen; Pengzhen Li; Penghui Fan; Lin Ma; Xinyu Cai; Yuchao Hou; Binbin Li; Jianyu Su (Food Microbiology, 2025)

Alkaline phosphatase-mediated hydrolysis of dissolved organic phosphorus enhances phosphorus cycling in the Yellow Sea - Xiaokun Ding; Haoyu Jin; Chao Zhang; Lei Lin; Xinyu Guo; Aobo Wang; Jie Shi; Xiaohong Yao; Huiwang Gao (Environmental Pollution, 2025)

Narrow-band green nitride phosphor for wide color gamut backlighting - Xinyu Zhang; Wanyuan Li; Chao Wang; Lin Zhang; Shuxing Li; Rong-Jun Xie (Chemical Engineering Journal, 2025)

Mendelian randomization analysis and molecular mechanism study of childhood asthma and obstructive sleep apnea - Xinyu Wang; Lin Zhang; Hao Chen; Ting Tian; Lulu Wu; Yuping Huang; Qian Cao; Lili Zhuang; Guoping Zhou (Human Genetics, 2025)

Insight on the optimized electronic structure of carbon nitride on ultrafast water treatment via photocatalytic activation of ferrate - Ningxuan Xue; Zhaobing Guo; Xinyu Gai; Yiyang Chen; Siyue He; Guanjie Lin; Fengling Liu; Shuai Zhang; Pengxiang Qiu (Journal of Hazardous Materials, 2025)

MnOOH/carbon-based reactive electrochemical membrane for aqueous organic pollutants decontamination - Zonglin Pan; Chunyu Wang; Xinyu Liu; Ruisong Xu; Hong Xin; Hang Yu; Lin Li; Shuaifei Zhao; Chengwen Song; Tonghua Wang (Journal of Environmental Management, 2025)

The mechanism of egg white protein to enhance the thermal gel properties of giant squid (Dosidicus gigas) surimi - Fuge Niu; Xiang Li; Chenyang Lin; Xinyu Hu; Bin Zhang; Weichun Pan (Food Chemistry, 2025)

Another inner truth of shaking: Water migration and transformation-advanced physicochemical alterations in tea leaves - Zhilong Hao; Jinyuan Wang; Jiayun Zhuang; Xinyu Feng; Helin Lv; Jiao Feng; Shuping Ye; Weisu Tian; Guanjun Pan; Ping Chen; Hongzheng Lin; Qiang Chu (Food Chemistry, 2025)

Rational design of membrane electrode assembly for durable anion exchange membrane water electrolysis - Lingjing Li; Chenxiao Lin; Xinyu Ma; Yichang Ma; Aimei Zhu; Zhaoxiong Xie; Qiugen Zhang (Chemical Engineering Journal, 2025)

Multilayer polyimide nanofibrous aerogels for efficient thermal insulation and piezoelectric sensor - Jianwei Li; Hui Li; Jun Lin; Yuyan Lu; Jiaxin Qin; Jinlong Gao; Xinyu Zhang; Qiangli Zhao (Chemical Engineering Journal, 2025)

C6orf120 Deficiency Inhibits Hepatic Stellate Cell Activation by Upregulating RARβ Signaling - Yingying Lin; Xin Wang; Xinyu Cui; Na Zhu; Yanyan Li; Xin Li (Cell Biochemistry and Biophysics, 2025)

Half-day (daytime and nighttime) precipitation extremes in China: Changes and attribution from 1981 to 2022 - Jiahao Han; Shibo Fang; Xiaomao Lin; Zhanhao Zhang; Man Li; Yanru Yu; Wen Zhuo; Xinyu Wang (Global and Planetary Change, 2025)

Ion type-based formation rules and functional properties of polysaccharide-starch aerogels with chitooligosaccharide, xanthan gum, and locust bean gum: A comparative study - Qian Lin; Wenqing Zhao; Wei Liang; Xinyu Wang; Jie Zeng; Haiyan Gao; Wenhao Li (Food Research International, 2025)

Inhibitory effect of L-arginine on the oxidative aggregation behavior of myofibrillar proteins in the Antarctic krill (Euphausia superba): pH and antioxidation - Xinyu Zhang; Xiang Ren; Junxin Lin; Peizi Sun; Yuting Tan; Dongmei Li (Food Chemistry, 2025)

Flowering in aged white tea: Recovering umami taste and amplifying of stale aroma - Wan Zhu; Xinyu Feng; Yani Pan; Haowei Guo; Yunqing Liu; Xingchen Lin; Fangyuan Fan; Shuying Gong; Ping Chen; Qiang Chu (Food Chemistry, 2025)

Marangoni-driven regional salt crystallization for high salinity desalination - Jinbu Su; Xuli Lin; Jinchi Ma; Chenyi Shi; Yunong Xie; Haizhou Xu; Yuyi Xu; Xinyu Dong; Weixin Du; Xiaoyu Cao; Chengbing Wang (Chemical Engineering Journal, 2025)

Marangoni-driven regional salt deposition in self-cleaning paper based evaporators for stable and high-performance desalination - Yunong Xie; Jinbu Su; Weixin Du; Chenrui Ji; Kuangtaibei Zhang; Jilun Wang; Yuyi Xu; Xuli Lin; Chenyi Shi; Xinyu Dong; Chengbing Wang (Chemical Engineering Journal, 2025)

Emerging metal halide perovskite for photoluminescence sensing: Transitioning photophysics into practical applications - Daocheng Hong; Xuanwen Xu; Xinyu Song; Lei Zhang; Lin Sun; Changzhou Yuan; Ruiyu Jiang (Chemical Engineering Journal, 2025)

Insomnia in Parkinson’s Disease: Causes, Consequences, and Therapeutic Approaches - Xiaoyu Duan; Hanshu Liu; Xinyu Hu; Qinwei Yu; Guiying Kuang; Long Liu; Shurui Zhang; Xinyi Wang; Jingwen Li; Danfang Yu; Jinsha Huang; Tao Wang; et al. (Molecular Neurobiology, 2025)

ds-FCRN: three-dimensional dual-stream fully convolutional residual networks and transformer-based global–local feature learning for brain age prediction - Yutong Wu; Chen Zhang; Xiangge Ma; Xinyu Zhu; Lan Lin; Miao Tian (Brain Structure and Function, 2025)

Inclusion Complex of Nimodipine with Sulfobutylether-β-cyclodextrin: Preparation, Characterization, In Vitro and In Vivo Evaluation - Jiahui Liu; Meichai Li; Yongjie Huang; Xinyu Wang; Youfa Xu; Zhiqin Fu; Zhizhe Lin; Jianming Chen; Xin Wu (AAPS PharmSciTech, 2025)

Nitrogen-driven shifts in molecular composition of soil dissolved organic matter linked to rare bacterial sub-communities - Xiaochun Yuan; Quanxin Zeng; Xinyu Bai; Xiaoqing Zhang; Xiaoting Fu; Mengxiao Ren; Juyan Cui; Qiufang Zhang; Xiaoli Gao; Jiacong Zhou; Yong Zheng; Kaimiao Lin; et al. (Science of The Total Environment, 2025)

A 3D Janus-like structure evaporator based on capillary force promoting efficient solar steam generation - Yunong Xie; Jinbu Su; Chenrui Ji; Yuyi Xu; Xuli Lin; Chenyi Shi; Weixin Du; Xinyu Dong; Chengbing Wang (Desalination, 2025)

Water-triggered stimuli-responsive luminescent crown-ether-coordinated cuprous bromides for multi-functional applications - Rui Wu; Hao Yang; Meifeng Jiang; Hui Tong; Xinyu Hu; Ziyang Liu; Chunhua Luo; Hui Peng; Hechun Lin (Chemical Engineering Journal, 2025)

Revealing the dynamic effects of land cover change on land surface temperature in global major bay areas - Qingtao Zhang; Yijia Guan; Xinyu Wu; Jingkun Zhang; Rui Li; Kairong Lin; Yongheng Wang (Building and Environment, 2025)

Tensile Bearing Performance and Mechanical Transfer Mechanism of Coal-Rock Composite Anchor Bodies Under Different Height Ratios of Rock to Coal - Pandong Zhang; Lin Gao; Xiaohe Wang; Yinwei Wang; Xinyu Zhan; Fanghao Zhao (Rock Mechanics and Rock Engineering, 2025)

Correction: The origin of summer high-salinity water in the southern Bay of Bengal and its interannual variabilities - Xinyu Lin; Yun Qiu; Wenshu Lin; Xutao Ni; Chunsheng Jing (Climate Dynamics, 2025)

Current status and trends of illegal trade in hawksbill turtle products in Hainan Island, China - Xinyu Ji; Zhao Wang; Ting Zhang; Dehui Chen; Wenxiang Yang; Meimei Li; Haitao Shi; Liu Lin (Frontiers in Marine Science, 2024)
Introduction Illegal wildlife trade is among the most profitable illegal businesses worldwide. The hawksbill turtle ( Eretmochelys imbricata ), which has been listed as Critically Endangered on the IUCN Red List, has long been a prominent target of illegal wildlife trading worldwide, thus posing a substantial threat to its continued survival. In China, although Hainan Island is the largest trading area and the most important transit point for the illegal trade of hawksbill turtles, very few investigations of this trade have been conducted here. Methods In this study, from 2019 to 2020, we conducted field investigations to assess the extent of the illegal trade in hawksbill turtle products in nine cities on Hainan Island. Results Among the 878 shops surveyed in 2019, 157 shops (17.9%) sold hawksbill turtle products, totaling 6,208 pieces. In 2020, 122 shops (13.6%) of 895 surveyed shops sold such products, totaling 1,821 pieces. Thus, these findings indicate that the number of shops selling hawksbill turtle products and the total number of products sold declined in 2020. Among the surveyed cities, the highest levels of illegal trade in hawksbill turtle products were recorded in Haikou and Sanya, the capital city of Hainan and a renowned tourist city, respectively. Jewelry and craft shops were found to produce the most products, accounting for 98.0% of the shops surveyed. Accessories such as bracelets and necklaces accounted for the highest proportions of hawksbill turtle products, representing 72.5% and 92.9% of the total in 2019 and 2020, respectively. Discussion The observed decline in illegal trade in 2020 can be attributed to a combination of factors, including a strengthening of government law enforcement and supervision after the COVID-19 pandemic, a shift in illegal trade from offline to online activities, and a reduction in tourists. Law enforcement agencies should continue strict enforcement and supervision to effectively combat illegal trade, particularly in the key trading areas of Haikou and Sanya. Additionally, authorities should emphasize public education to increase awareness of wildlife conservation and relevant legislation. The findings of this study will serve as a vital reference for relevant law enforcement agencies, contributing to the effective combatting and prevention of the illegal hawksbill turtle trade in China.

Bacterial and fungal keystone taxa play different roles in maintaining community resistance and driving soil organic carbon dynamics in response to Solidago Canadensis invasion - Jiaoyang Zhang; Xiao Lin; Xinyu Zhang; Hui Huang; Yueling Qi; Zhen Zhang; Baodong Chen; Elly Morriën; Yongguan Zhu (Science of The Total Environment, 2024)

The efficient ferrate activation by Co modified N-doped carbon nanosheets for the ultrafast water treatment - Siyue He; Ningxuan Xue; Guanjie Lin; Yiyang Chen; Xinyu Gai; Yalin Yu; Fengling Liu; Zhaobing Guo; Pengxiang Qiu (Journal of Environmental Chemical Engineering, 2024)

Oerskovia flava sp. nov., a deoxynivalenol (DON)-degrading actinomycete isolated from the rhizosphere soil of long-term continuous cropping cucumber - Wei Wei; Wenjun Guo; Biyue Yang; Kaili Wang; Xinyu Hu; Guanya Ji; Xiangru Xu; Shenkui Liu; Lin Zhu (Antonie van Leeuwenhoek, 2024)

Nocardioides limicola sp. nov., an alkaliphilic alkane degrading bacterium isolated from oilfield alkali-saline soil - Lin Zhu; Biyue Yang; Wenjun Guo; Xinyu Hu; Shenkui Liu; Xiang Xiao; Wei Wei (Antonie van Leeuwenhoek, 2024)

Tibetan lake sediment records reveal historical emission and long-range atmospheric transport of chlorinated paraffins - Jun Li; Bo Yuan; Qian Li; Xinyu Du; Ruwen Chang; Guo-Li Yuan; Yan Wu; Tian Lin (Water Research, 2024)

Visible-light-response Fe-doped BiOCl microspheres with efficient photocatalysis-Fenton degradation of antibiotics - Yuxin Zha; Xinyu He; Yiding Wang; Wangyang Chen; Lin Chen; Liguang Chen; Songxue Wang; Boyin Yan; Bingrui Ma; Jincheng Li (Journal of Water Process Engineering, 2024)

Effect of electron beam pretreated wheat flour on dough properties - Li Niu; Mengting Yan; Wei Liang; Qian Lin; Qi Zhao; Ruijie Li; Xinyu Wang; Raushan Moldakhmetova; Wenhao Li (Journal of Cereal Science, 2024)

Uncovering the Shuixian tea grades hierarchy in Chinese national standard: From sensory evaluation to microstructure and volatile compounds analysis - Yanping Lin; Yibiao Huang; Xia Liu; Yani Pan; Xinyu Feng; Haowei Guo; Xiaolan Li; Yike Tao; Ping Chen; Qiang Chu (Food Chemistry, 2024)

Exploration and application of treating OSCC by a precisely concentrated synergistic agent in combination with thermally responsive release of effective therapeutic dosages of cisplatin - Shilin Guo; Tao Liu; Xinyuan Peng; Xinyu Zhang; Yangguang Li; Linzhong Yang; Wenguang Xu; Zheng Wei; Diya Xie; Lin Chen; Zichen Cao; Xiteng Yin; et al. (Chemical Engineering Journal, 2024)

Fabrication of Fe-Ti heteroatom-based metal-organic framework with vantage defects for high-efficient arsenic removal from water - Shanshan Shang; Xinyu Chen; Chao Yang; Ying Zhou; Kaimin Shih; Lin Lin; Xiao-yan Li (Chemical Engineering Journal, 2024)

Liquid–Liquid Phase Separation within Dense-Core Vesicles in Sympathetic Adrenal Chromaffin Cells - Quanfeng Zhang; Zhaohan Lin; Xinyu Du; Zhuan Zhou (Neuroscience Bulletin, 2024)

A hybrid genetic tabu search algorithm for distributed job-shop scheduling problems - Jin Xie; Liang Gao; Xinyu Li; Lin Gui (Swarm and Evolutionary Computation, 2024)

Oxygen evolution reaction enhancing electrochemical performance of V-doped Ni(OH)2 for aqueous asymmetric supercapacitors - Ting Xiao; Hongxiang Lin; Can Tang; Xiuru Li; Yuting Mei; Lin Gao; Lihua Jiang; Peng Xiang; Shibing Ni; Yequan Xiao; Xinyu Tan (Chemical Engineering Journal, 2024)

Screening of polyurethane-degrading microbes using a quenching fluorescence probe by microfluidic droplet sorting - Wei Xia; Haohong Lin; Xinyu Zhou; Yihu Wang; Shixiang Cao; Jiawei Liu; Anming Xu; Weiliang Dong; Min Jiang (Chemosphere, 2024)

Exploration of port environmental efficiency measurement and influential factors in the Yangtze River Delta Pilot Free Trade Zone - Xinyu Lin; Xiaodong Jing; Fei Cheng; Min Wang (Marine Pollution Bulletin, 2024)

Investigation on phytoplankton dynamics and its environmental correlates in the Xiangjiaba channel-type reservoir - Xinlu Wang; Jian Sun; Binliang Lin; Lidi Shi; Xinyu Zuo; Yuanyi Li (Journal of Hydrology, 2024)

Bamboo vinegar regulates the phytoremediation efficiency of Perilla frutescens (L.) Britt. by reducing membrane lipid damage and increasing cadmium retention - Zhenguo Li; Xingyu Hao; Tianlian He; Ying Chen; Mingwei Yang; Cheng Rong; Chengzhen Gu; Qingtie Xiao; Ruiyu Lin; Xinyu Zheng (Journal of Hazardous Materials, 2024)

The origin of summer high-salinity water in the southern Bay of Bengal and its interannual variabilities - Xinyu Lin; Yun Qiu; Wenshu Lin; Xutao Ni; Chunsheng Jing (Climate Dynamics, 2024)

Identification of phase-I and phase-II metabolites and the metabolic pathway of the novel synthetic cannabinoid 5F-EDMB-PICA in vitro - Yujie Gao; Kaiting Shi; Peipei Wang; Xinyu Liu; Chenxi Liu; Liya Luo; Yanchen Lin; Lin Yang; Rongji Yang; Linchuan Liao (Archives of Toxicology, 2024)

Assessing the degree of impact from iceberg activities on penguin colonies of Clarence Island - Hong Lin; Xiao Cheng; Teng Li; Qian Shi; Qi Liang; Xinyu Meng; Shaoyin Wang; Lei Zheng (Acta Oceanologica Sinica, 2024)

High-value utilization of boron mud waste: preparation of magnesium oxysulfate cement after primary blank roasting and secondary (NH4)2SO4 roasting - Jing Wen; Hongyu Sui; Tao Jiang; Lin Li; Xinyu An (Process Safety and Environmental Protection, 2024)

Bi-reforming of model biogas into syngas over layered double hydroxides-derived bimetallic Ni-Ga catalysts - Wenyang Li; Guofeng Zhao; Xinyu Huang; Weiting Lin; Jun Xie; Jiawei Zhong (Fuel, 2024)

Active prelithiation strategies for advanced lithium storage systems: A perspective from electrochemical mechanism to structural design and application - Bo Jin; Keyu Zhang; Geng Gao; Qing Zhao; Xinyu Jiang; Dingfang Cui; Keqi Chen; Xiang Lin; Liuliu Liu; Rui Yan; Bin Yang; Yaochun Yao (Chemical Engineering Journal, 2024)

Evolution characteristics and mechanisms of the spring warm pool in the Bay of Bengal - Wenshu Lin; Yun Qiu; Xutao Ni; Xinyu Lin; Tongtong Liu (Frontiers in Marine Science, 2024)
Knowledge of spring warm pool in the Bay of Bengal (BoBWP) is key for further understanding the climate variability in this region and beyond, but little is known about the BoBWP climatological state and the related mechanisms. In this study, we investigate the spatial structure and evolution of the BoBWP using daily Optimum Interpolation SST data from 1982-2022 in combination with multi-source data. Our analysis shows that the BoBWP is located in the central bay (6°-13°N) with a thickness around 20 m ~ 40 m. Composite analysis indicates that the BoBWP emerges in early April, peaks in early May and dissipates in early June. During the developing period, the net heat flux dominates the formation of spring warm pool through significant air-sea coupling processes, and induces the warming rate of 0.27°C/10d in the mixed layer, which is far larger than the contribution of oceanic dynamical processes (0.01°C/10d). During the decaying period, the net heat flux also plays a dominant role, with a cooling rate of -0.21°C/10d, meanwhile ocean dynamical processes contribute to the cooling of the warm pool with a rate of -0.01°C/10d. Additionally, the SST and the area of the BoBWP are significantly correlated with ENSO (r=0.66 and 0.73, p=0.05). During El Niño decaying year, the BoBWP primarily expands in a southward direction, with a 75% increase in area. Conversely, during La Niña decaying year, the BoBWP almost disappears, with a 52% decrease.

A newly-discovered tea population variety processed Bai Mu Dan white tea: Flavor characteristics and chemical basis - Yanping Lin; Yibiao Huang; Su Zhou; Xiaolan Li; Yike Tao; Yani Pan; Xinyu Feng; Haowei Guo; Ping Chen; Qiang Chu (Food Chemistry, 2024)

Regeneration of sedimentary manganese in coastal sediments deciphered by 224Ra/228Th disequilibria - Zhongliang Lin; Li Liu; Ergang Lian; Weiqiang Zhao; Xinyu Jiang (Science of The Total Environment, 2024)

Metabolome and transcriptome reveal high abundance of bioactive substances in albino jujube fruit as potential function food - Yang Wang; Yong Huang; Panhui Song; Xuemei Peng; Xinyu Li; Rong Su; Hui Zhang; Lijin Lin; Hui Xia; Qunxian Deng (Food Bioscience, 2024)

Whole-rock geochemical and zircon U-Pb-Hf isotopic compositions of the Yunlougang and Wucun granitic plutons in the Hetai area of South China: Implications for petrogenesis and geodynamic setting - Lixing Wang; Deru Xu; Hai Lin; Xinyu Wang; Genwen Chen; Qianqian Jiao (Geochemistry, 2024)

Rhythmic mild photothermal therapy enhancing anti-PD-L1 response for oral squamous cell carcinoma immunotherapy - Tao Liu; Shilin Guo; Dongyao Zhang; Diya Xie; Xinyu Zhang; Lin Chen; Yanyi Wang; Huihui Zou; Linzhong Yang; Meng Zhou; Xin Tong; Jianchuan Ran; et al. (Chemical Engineering Journal, 2024)

An antibacterial membrane based on Janus bacterial cellulose with nano-sized copper oxide through polydopamine conjugation for infectious wound healing - Bing Han; Fan Liu; Shuhang Hu; Xinyu Chen; Chenming Lin; In-Seop Lee; Cen Chen (Carbohydrate Polymers, 2024)

Effect of Salinity on the Development and Dormancy of Cladonema digitatum - Shen Lin; Xinyu Fang; Xiaopeng Zhong; Xulin Zhang; Jianming Chen; Konglin Zhou (Estuaries and Coasts, 2024)

Preferential remineralization of phosphorus from organic matter in river-dominated coastal sediments - Zhongliang Lin; Li Liu; Ergang Lian; Xinyu Jiang (Science of The Total Environment, 2024)

Borneol serves as an adjuvant agent to promote the cellular uptake of curcumin for enhancing its photodynamic fungicidal efficacy against Candida albicans - Zhenlong Zhou; Shengli Wang; Penghui Fan; Xiaofeng Meng; Xinyu Cai; Wen Wang; Lin Ma; Hang Ma; Jianyu Su (Journal of Photochemistry and Photobiology B: Biology, 2024)

Catalytic hydrodeoxygenation of 5-hydroxymethylfurfural to 2,5-dimethylfuran over Pd-Co bimetallic catalysts supported on MoCx - Yu Chen; Haoquan Guo; Junye Yang; Kaiyang Xu; Xinyu Lu; Yue Yang; Hongqiao Lin; Lizhi Wu; Li Tan; Guohui Yang; Noritatsu Tsubaki; Xiaoli Gu; et al. (Fuel, 2024)

SERS lateral flow strip detection of serum biomarkers for noninvasive assessment of operative microwave ablation outcomes of unresectable hepatocellular carcinoma - Xiaoming Su; Xinyu Liu; Yuzhen Ouyang; Yangcenzi Xie; Mingyang Chen; Pan Chen; Jia Liu; Minghua Wu; Chien-hong Lin; Hong Zhong; Ming Li (Chemical Engineering Journal, 2024)

Emerging role of lncRNAs as mechanical signaling molecules in mechanotransduction and their association with Hippo-YAP signaling: a review - Siyi Lin; Xinyu He; Ying Wang; Yu Chen; Aifu Lin (Journal of Zhejiang University-SCIENCE B, 2024)

Active dark carbon fixation evidenced by 14C isotope assimilation and metagenomic data across the estuarine-coastal continuum - Bolin Liu; Yanling Zheng; Xinyu Wang; Lin Qi; Jie Zhou; Zhirui An; Li Wu; Feiyang Chen; Zhuke Lin; Guoyu Yin; Hongpo Dong; Xiaofei Li; et al. (Science of The Total Environment, 2024)

FvDFR2 rather than FvDFR1 play key roles for anthocyanin synthesis in strawberry petioles - Xinyu Li; Xi Luo; Zhongchi Liu; Chong Wang; Anqi Lin; Kun Xiao; Minghao Cao; Junmiao Fan; Hongli Lian; Pengbo Xu (Plant Science, 2024)

Selenium deficiency exacerbated Bisphenol A-induced intestinal toxicity in chickens: Apoptosis and cell cycle arrest mediated by ROS/P53 - Dongliu Luo; Xinyu Tang; Yixuan Wang; Shuqi Ying; Yujiao He; Hongjin Lin; Pervez Ahmed Khoso; Shu Li (Science of The Total Environment, 2024)

Regeneration of sedimentary phosphorus and iron in a large seasonally hypoxic estuary deciphered by 224Ra/228Th disequilibria - Zhongliang Lin; Yilin Cheng; Ergang Lian; Tong Wu; Lin Wei; Xiangming Shi; Xinyu Jiang; Liuting Yuan; Shouye Yang; Pinghe Cai (Marine Chemistry, 2024)

Nitrite self-degradation process in radish paocai under the synergistic regulation of prokaryotic microorganisms - Xinyu Hu; Wei Wei; Jiayan Zhang; Songtao Fan; Yufeng He; Juan Bai; Ying Zhu; Yansheng Zhao; Lin Zhu; Xiang Xiao (Food Bioscience, 2024)

Highly selective removal of triarylmethane dyes by molecular switched adsorbents via charge-assisted hydrogen bond - Xinyu Song; Jiabin Lu; Meipin Liu; Lanqin Tang; Lin Sun; Ruiyu Jiang; Lei Zhang (Chemical Engineering Journal, 2024)

Synthesis of gel crosslinked composite material from spent cathode carbon blocks and its application in modified asphalt binders - Xinyu Li; Denghui Ren; Shencheng Fan; Zibo Lin; Fanyu Meng; Haisheng Wu; Fang Lai; Jing Li (Journal of Cleaner Production, 2024)

Micro assembly strategies for enhancing solid-state emission of cellulose nanocrystals and application in photoluminescent inks - Zhenxu Shi; Dimei Yang; Yan Zhou; Xinyu Chen; Lin Gan; Jin Huang (Carbohydrate Polymers, 2024)

Single-Cell Mapping of Brain Myeloid Cell Subsets Reveals Key Transcriptomic Changes Favoring Neuroplasticity after Ischemic Stroke - Fangxi Liu; Xi Cheng; Chuansheng Zhao; Xiaoqian Zhang; Chang Liu; Shanshan Zhong; Zhouyang Liu; Xinyu Lin; Wei Qiu; Xiuchun Zhang (Neuroscience Bulletin, 2024)

Matrine Mediated Immune Protection in MS by Regulating Gut Microbiota and Production of SCFAs - Mengmeng Dou; Yaojuan Chu; Xueliang Zhou; Mengru Wang; Xinyu Li; Rui Ma; Zhirui Fan; Xiaoyu Zhao; Wenbin Wang; Silu Li; Ying Lv; Lin Zhu (Molecular Neurobiology, 2024)

Lower Cretaceous volcanic-sedimentary successions of the continental rift basin in the Songliao Basin, northeast China: Implication in high-quality reservoir prediction and hydrocarbon potential - Cong Hu; Qingjie Deng; Lin Lin; Mingyi Hu; Xinyu Hou; Limin Zong; Peng Song; Oumar Ibrahima Kane; Quansheng Cai; Zhonggui Hu (Marine and Petroleum Geology, 2023)

A study of the thermal comfort in urban mountain parks and its physical influencing factors - Yisha Liu; Yumao Lai; Lin Jiang; Bin Cheng; Xinyu Tan; Fanxi Zeng; Shuang Liang; Aoyan Xiao; Xiaowei Shang (Journal of Thermal Biology, 2023)

Impact of L-arginine on the quality of heat-treated Antarctic krill: Influence of pH and the guanidinium group - Xiang Ren; Xinyu Zhang; Peizi Sun; Junxin Lin; Yuying Zhang; Dongmei Li (Food Research International, 2023)

Covalent codeposition modification of reverse osmosis membranes with Noria and zwitterionic copolymers for antifouling in reclaimed water production - Xinyu Zhang; Zhenglun Lin; Daoji Wu; Ming Xie; Jingtao Xu; Xian Bao; Xiaoxiang Cheng; Ying Wang; Feiyong Chen (Desalination, 2023)

Aged polycyclic aromatic hydrocarbons as stratigraphic marker in the Anthropocene: Evidence from Tibetan Lake sediments - Jun Li; Ruwen Chang; Xiyu Ban; Guo-Li Yuan; Xinyu Du; Ge Yin; Tian Lin (Water Research, 2023)

Novel and legacy brominated flame retardants in snakes and frogs: Tissue distribution, biomagnification, and maternal transfer - Guanzhen Sun; Xinyu Du; Yan Wu; Ge Yin; Luting Chen; Xiaojun Liu; Yihui Zhou; Yanling Qiu; Tian Lin (Science of The Total Environment, 2023)

Hydrodynamic effects of the flow-induced vibrations on the mass transfer and permeate flux in a desalination membrane - Xiao Hu; Xinyu Li; Sanchuan Yu; Peifeng Lin; Zuchao Zhu (Desalination, 2023)

The s-oph enzyme for efficient degradation of polyvinyl alcohol: soluble expression and catalytic properties - Xinyu Wang; Jiaxuan Li; Xiaoshan Lin; Yi Zhang (Molecular Biology Reports, 2023)

Self-similarity convolution neural network for seismic noise suppression in desert environment - Hongbo Lin; Xinyu Xu; Shigang Wang (Studia Geophysica et Geodaetica, 2023)

Depositional and diagenetic controls over reservoir quality of tight sandstone and conglomerate in the lower Cretaceous Shahezi formation, Xujiaweizi fault depression, Songliao basin, China - Nengwu Zhou; Jiamin Lu; Shuangfang Lu; Pengfei Zhang; Min Wang; Zizhi Lin; Xinyu Jiang; Yang Liu; Guangshun Xiao (Marine and Petroleum Geology, 2023)

Electrochemical CO2 reduction to C2+ products with Cu-oleylamine based nanoparticles synthesized by simple thermal treatment - Xinyu Liu; Jingzheng Li; Yuan Xue; Mingxing Gong; Carlos R. Cabrera; Lin Yao; Zhongfa Hu (Fuel, 2023)

Does urban scale borrowing aggravate carbon and air pollution emissions? - Zhongyao Cai; Xuhui Ding; Huaxing Lin; Ziqian Zhou; Xinyu Yang; Ping Jiang (Environmental Impact Assessment Review, 2023)

Shikonin suppresses small cell lung cancer growth via inducing ATF3-mediated ferroptosis to promote ROS accumulation - Xinyu Qian; Lin Zhu; Mengzhen Xu; Haoli Liu; Xinyan Yu; Qiuyue Shao; Jing Qin (Chemico-Biological Interactions, 2023)

Association of long-term exposure to ambient PM2.5 and its constituents with gut microbiota: Evidence from a China cohort - Sicheng Li; Bing Guo; Ke Dong; Shourui Huang; Jialong Wu; Hanwen Zhou; Kunpeng Wu; Xinyu Han; Xian Liang; Xiaofang Pei; Haojiang Zuo; Hualiang Lin; et al. (Science of The Total Environment, 2023)

A simulation-based approach for assessing regional and industrial flood vulnerability using mixed-MRIO model: A case study of Hubei Province, China - Xinyu Jiang; Yue Lin; Lijiao Yang (Journal of Environmental Management, 2023)

A rapid approach to evaluating ground surface conditions for shale gas extraction in mountainous areas - Xiaofeng Xu; Wanzhong Shi; Xinyu Zhang; Jianwei Lin; Wanjun Lu; Qian Feng; Xianglin Chen; Ren Wang; Xiaoming Zhang (Gas Science and Engineering, 2023)

Green space exposure on depression and anxiety outcomes: A meta-analysis - Ziquan Liu; Xuemei Chen; Huanhuan Cui; Yuxuan Ma; Ning Gao; Xinyu Li; Xiangyan Meng; Huishu Lin; Halidan Abudou; Liqiong Guo; Qisijing Liu (Environmental Research, 2023)

The association between chemical constituents of ambient fine particulate matter and obesity in adults: A large population-based cohort study - Shaokun Yang; Feng Hong; Sicheng Li; Xinyu Han; Jiawei Li; Xing Wang; Lin Chen; Xuehui Zhang; Xi Tan; Jingru Xu; Zhuoma Duoji; Zhuoga Ciren; et al. (Environmental Research, 2023)

Benchmark dose estimation for benzene-exposed workers in China: Based on quantitative and multi-endpoint genotoxicity assessments - Yiyi Cao; Tongshuai Wang; Jing Xi; Wei Tian; Weiying Liu; Yuan Sun; Wuzhong Liu; Xinyue You; Anqi Li; Guanghui Zhang; XinYu Zhang; Zhao-lin Xia; et al. (Environmental Pollution, 2023)

Three-Dimensional Climatological Structures of the Arabian Sea Eddies and Eddy-Induced Flux - Xinyu Lin; Yun Qiu; Xutao Ni; Wenshu Lin; Cherry Aung (Journal of Ocean University of China, 2023)

Nighttime light perspective in urban resilience assessment and spatiotemporal impact of COVID-19 from January to June 2022 in mainland China - Yaohui Liu; Wenyi Liu; Xinyu Zhang; Yu Lin; Guoqiang Zheng; Zhan Zhao; Hao Cheng; Lutz Gross; Xiaoli Li; Benyong Wei; Fei Su (Urban Climate, 2023)

Soy protein isolate-citrus pectin-gallic acid ternary composite high internal phase Pickering emulsion for delivery of β-carotene: Physicochemical, structural and digestive properties - Xinyu Xu; Lin Li; Chunmin Ma; Dan Li; Yang Yang; Xin Bian; Jing Fan; Na Zhang; Feng Zuo (Food Research International, 2023)

Selenium Deficiency Induces Inflammatory Response and Decreased Antimicrobial Peptide Expression in Chicken Jejunum Through Oxidative Stress - Yujiao He; Lin Peng; Xiaochun Zhao; Xue Fan; Xinyu Tang; Guangliang Shi; Shu Li (Biological Trace Element Research, 2023)

Physiological response of red macroalgae Pyropia yezoensis (Bangiales, Rhodophyta) to light quality: a short-term adaptation - Xuefeng Zhong; Shuai Che; Congying Xie; Lan Wu; Xinyu Zhang; Lin Tian; Chan Liu; Hongbo Li; Guoying Du (Algae, 2023)
Light quality is a common environmental factor which influences the metabolism of biochemical substances in algae and leads to the response of algal growth and development. Pyropia yezoensis is a kind of economic macroalgae that naturally grows in the intertidal zone where the light environment changes dramatically. In the present study, P. yezoensis thalli were treated under white light (control) and monochromatic lights with primary colors (blue, green, and red) for 14 days to explore their physiological response to light quality. During the first 3 days of treatment, P. yezoensis grew faster under blue light than other light qualities. In the next 11 days, it showed better adaptation to green light, with higher growth rate and photosynthetic capacity (reflected by a higher rETRmax = 61.58 and Ek = 237.78). A higher non-photochemical quenching was observed in the treatment of red light than others for 14 days. Furthermore, the response of P. yezoensis to light quality also results in the difference of photosynthetic pigment contents. The monochromatic light could reduce the synthesis of all pigments, but the reduction degree was different, which may relate to the spectral absorption characteristics of pigments. It was speculated that P. yezoensis adapted to a specific or changing light environments by regulating the synthesis of pigments to achieve the best use of light energy in photosynthesis and premium growth and metabolism.

Enhancing the Thermotolerance of Isochrysis zhangjiangensis Through Co-culturing With Algoriphagus marincola - Simin Xu; Jiayi Cao; Minnan Wu; Yijun Xu; Yuanyuan Wu; Kaixi Shang; Bin Ma; Lin Zhang; Deshui Chen; Xinyu Liu; Xiaojun Yan; Jilin Xu (Marine Biotechnology, 2023)

The role of climate literacy in individual response to climate change: evidence from China - Wu-Lin Pan; Ruguo Fan; Wei Pan; Xinyu Ma; Cheng Hu; Piao Fu; Jingyi Su (Journal of Cleaner Production, 2023)

Theoretical determination method and field verification of the fracture position of the main roof of the gob-side coal-rock roadway in gently inclined coal seam - Xinyu Zhan; Lin Gao; Pengze Liu; Zhiqiang Zhao; Pandong Zhang; Ping Liu; Yongyin Wang (Bulletin of Engineering Geology and the Environment, 2023)

Structural, mechanical and thermal properties of cubic bixbyite-structured high-entropy oxides - Xinyu Ping; Bin Meng; Xiaohua Yu; Zhiyuan Ma; Xiaoyu Pan; Wu Lin (Chemical Engineering Journal, 2023)

July 2020 heavy rainfall in Japan: effect of real-time river discharge on ocean circulation based on a coupled river-ocean model - Yu-Lin K. Chang; Sergey M. Varlamov; Xinyu Guo; Toru Miyama; Yasumasa Miyazawa (Ocean Dynamics, 2023)
In July 2020, a stationary atmospheric front over Japan caused persistent, nearly continuous rain for most of the month that resulted in new historical highest rainfall records in several areas and caused serious river floods, landslides, and debris-flow events. An existing hindcast and forecast ocean circulation model that includes climatological discharge information of major rivers failed to represent the extreme river discharge under heavy rainfall. New experiments were conducted using real-time river discharge information based on Today's Earth CaMa-Flood simulation that includes 368 rivers in Japan. The inclusion of real-time river discharge improved the salinity bias in the near-surface waters. The differences were significant compared to the observations in the heavy rain region (i.e., Ariake Bay and Tosa Bay), and insignificant at offshore stations. The ensemble experiments of real-time river discharge cases suggested the difference between the climatological and the real-time river discharge experiments was not random, but was robust. The freshening water changed the shelf circulation, and its far-reaching effect appeared hundreds of kilometers away from the shore. Passive particle tracking was conducted for examining the cross-shelf exchange. More particles released from Bungo Channel went offshore in near-surface water when the real-time river discharge was used compared to using the climatology discharge. Particles released in Tosa Bay, Seto Inland Sea, and Kii Channel showed the opposite tendency. The real-time river discharge not only changed the modeled coastal salinity distribution, but also the coastal and offshore currents. The role of the real-time river discharge on modeling normal flow periods or drought events, and its influence on a longer time scale model simulation remain to be explored.

Double-negative T cells: a promising avenue of adoptive cell therapy in transplant oncology - Zhihang Hu; Modan Yang; Hao Chen; Chiyu He; Zuyuan Lin; Xinyu Yang; Huigang Li; Wei Shen; Di Lu; Xiao Xu (Journal of Zhejiang University-SCIENCE B, 2023)

Characteristics and mechanisms of the intraseasonal variability of sea surface salinity in the southeastern Arabian Sea during 2015–2020 - Hui Teng; Yun Qiu; Xinyu Lin; Xiwu Zhou (Acta Oceanologica Sinica, 2023)

Preliminary studies of the tardigrada communities from a polymetallic nodule area of the deep South China Sea - Xiaogu Wang; Lifen Bai; Chunsheng Wang; Bo Lu; Yujie Li; Qinyi Lin; Xinyu Huang; Paulo Fontoura (Frontiers in Marine Science, 2023)
Knowledge about marine tardigrades from the South China Sea is very scarce, with only four species from shallow waters recorded to date. The present study investigated the structure and diversity of tardigrade communities from the deep sea (1517-1725 m) at 8 stations in a polymetallic nodule area of the northern South China Sea. A total of 151 arthrotardigrades were collected belonging to 11 genera ( Angursa, Batillipes, Coronarctus, Euclavarctus, Exoclavarctus, Halechiniscus, Moebjergarctus, Raiarctus, Rhomboarctus, Tanarctus and Tholoarctus ), representing 17 species. Two Angursa species ( Angursa sp. 4 and Angursa sp. 3) were the most abundant (25.2% and 14.6%, respectively), followed by Moebjergarctus sp. (13.9%). Specimens were mostly (90.7%) distributed in the upper layer of the sandy-mud sediment (0-1 cm). The SIMPROF test showed that the composition of tardigrade communities at all stations was not significantly different. At different stations, the number of species, Shannon-Wiener diversity index and Pielou’s evenness index ranged from 4 to 10, 1.94 to 2.87, and 0.75 to 1.00, respectively. The average taxonomic distinctness (Δ+) ranged from 72.50 to 90.00, and the variation in taxonomic distinctness (Λ+) ranged from 316.67 to 1181.25. This study provides some basic information about the biodiversity of the marine tardigrade community in the South China Sea.

Effect of sloping bottom on river plume dynamics on a laboratory-scale rotating table - Yeping Yuan; Xinyu Tan; Ying-Tien Lin (Frontiers in Marine Science, 2023)
In nature, plumes usually enter the coastal ocean after they leave the estuary, and most of them interact with the continental shelf slope. To understand plume dynamics, laboratory experiments were carried out on a rotating table to simulate the evolution of plumes over a sloping bottom. We modified reduced gravity g’ , Coriolis parameter f , and shelf slope α to study their impacts on plume characteristics and freshwater fate, and used the optical thickness method to obtain the depth field. We found that with the increasing g’ or decreasing f , plume maximum depth h max decreases and plume maximum width W max increases. We proposed a method to determine plume types based on their attachment to the shelf slope: when PCN (plume classification number) > 1.6, the plume is bottom-attached; when PCN< 1.6, the plume is surface-advected. In addition, we found the bulge will become unstable when BIN (bulge instability number)< 0.8. Our analysis shows that the sloping bottom is the most significant factor determining the ratio of freshwater accumulated in the bulge over transported with coastal currents. Generally, bottom-attached plume trapped near the coast inhibits offshore freshwater transport and promotes coastal current transport, while baroclinic instability tends to produce a large cyclonic vortex over a gentle slope which strongly enhances the offshore transport.

Endocrine disrupting effect and reproductive toxicity of the separate exposure and co-exposure of nano-polystyrene and diethylstilbestrol to zebrafish - Xinyu Lin; Yuanning Wang; Xianhai Yang; Peter Watson; Feifei Yang; Huihui Liu (Science of The Total Environment, 2023)

Financial market risk and innovation nexus with growth: Channelizing the role of natural resources volatility for United States - Xinyu Ye; Runtian Lin (Resources Policy, 2023)

A portable paper-based aptasensor for simultaneous visual detection of two mycotoxins in corn flour using dual-color upconversion nanoparticles and Cu-TCPP nanosheets - Xianfeng Lin; Changxin Li; Xinyu Tong; Nuo Duan; Zhouping Wang; Shijia Wu (Food Chemistry, 2023)

Reducing manufacturing carbon emissions: Optimal low carbon production strategies respect to product structures and batches - Jun Zheng; Junjie Shi; Feng Lin; Xinyu Hu; Qi Pan; Tiening Qi; Yicheng Ren; Aizhi Guan; Zhiyi Zhang; Wei Ling (Science of The Total Environment, 2023)

Feasibility of reuse of modified electrolytic aluminium spent refractory material in asphalt and assessment of its environmental stability - Hao Tu; Xinyu Li; Yaseen Muhammad; Xin Jin; Hongfei Lin; Ruinan Pei; Zhenxia Zhao; Jing Li (Journal of Cleaner Production, 2023)

Activating the photocatalytic activity of insulator barium silicate: A liquid-phase alkalized tetracycline photosensitizer and its self-destruction - Xueli Hu; Peng Lu; Min Fu; Yongheng Zhang; Xinyu Cao; Jiabo Chen; Shutao Lin; Juanjuan Yao; Zhi Zhang (Chemical Engineering Journal, 2023)

Liver Organoids, Novel and Promising Modalities for Exploring and Repairing Liver Injury - Chiyu He; Di Lu; Zuyuan Lin; Hao Chen; Huigang Li; Xinyu Yang; Modan Yang; Kai Wang; Xuyong Wei; Shusen Zheng; Xiao Xu (Stem Cell Reviews and Reports, 2023)

Combined effects of climatic change and hydrological conditions on thermal regimes in a deep channel-type reservoir - Lidi Shi; Khosro Morovati; Jian Sun; Binliang Lin; Xinyu Zuo (Environmental Monitoring and Assessment, 2023)

Selenium deficiency increased duodenal permeability and decreased expression of antimicrobial peptides by activating ROS/NF-κB signal pathway in chickens - He Yujiao; Tang Xinyu; Fan Xue; Li Zhe; Peng Lin; Shi Guangliang; Li Shu (BioMetals, 2023)

A new diterpenoid alkaloid from Delphinium gyalanum C. Marquand & Airy Shaw - Xinyu Li; Meizhen Ye; Feng Gao; Xianli Zhou; Lin Chen; Shuai Huang (Natural Product Research, 2023)

The effect of underwater supplemental light on the growth of V.spinulosa Yan and the restoration process of water - Jinshan Zhao; Pu Yang; Yuye Lin; Xiaoyao Zhu; Jiaxin Wang; Xinyu Gan; Xiangyong Zheng; Min Zhao; Chunzhen Fan; Linna Du; Huanyi Miu (Process Safety and Environmental Protection, 2023)

Sulfate-enhanced low-temperature activity of Pt/γ-Al2O3 for landfill gas deoxygen - Xinyu Yang; Zezhi Chen; Huijuan Gong; Feng Lin; Tingting Zhu; Ziyi Yang (Fuel, 2023)

Arsenic shapes the microbial community structures in tungsten mine waste rocks - Xiaolong Lan; Wenjie Lin; Zengping Ning; Xinyu Su; Yushuang Chen; Yanlong Jia; Enzong Xiao (Environmental Research, 2023)

Electrosprayed thin film nanocomposite polyamide nanofiltration with homogeneous distribution of nanoparticles for enhanced separation performance - Yingyao He; Jianqiang Wang; Xinyu Fu; Haibo Lin; Weilin Zhang; Xiao Wang; Fu Liu (Desalination, 2023)

Dual-targeting celecoxib nanoparticles protect intestinal epithelium and regulate macrophage polarization for ulcerative colitis treatment - Ruijie Chen; Xinlu Lin; Qian Wang; Xingsi An; Xinyu Zhao; Yujie Lin; Tuyue Sun; Chenyang Yan; Aimin Cai; Weilan Cao; Youting Zhang; Qing Yao; et al. (Chemical Engineering Journal, 2023)

Surface adsorption guided design of semicrystalline nickel-iron hydroxide for highly-sensitive glucose sensing - Minyuan Tan; Ming Ni; Xinyu Liu; Bo Qu; Xi Lin; Daochuan Jiang; Yupeng Yuan; Haiwei Du (Chemical Engineering Journal, 2023)

Phycospheric bacterial community structure and function succession during the typical harmful macroalgal blooms - Tongfei Qu; Chengzong Hou; Chen Guan; Xinyu Zhao; Jun Chen; Yi Zhong; Jinhui Xu; Zhihao Lin; Yu Xu; Xuexi Tang; Ying Wang (Frontiers in Marine Science, 2022)
Based on the diversity and importance of phycospheric microorganisms as well as their complex interaction with algae, their ecological correlation with algal bloom events has become a research topic of great interest that remains unclear in the natural dynamic process of harmful macroalgal blooms (HMBs). The world’s largest green tides caused by macroalgae Ulva prolifera have occurred in the Yellow Sea for 16 consecutive years, and seriously affected the coastal ecosystem. Here, we monitored the spatiotemporal dynamics of the phycospheric bacterial community during the U . prolifera green tide bloom. The 73-day continuous field survey covered the whole process of initial invasion until the extinction of the green tide. The phycospheric bacterial community has a higher richness than the control seawater bacteria; in addition, it has more enriched taxa with organic nutrition preference and environmental pressure adaption, such as Bacteroidetes, Firmicutes, and Desulfobacterota. The same differences in populations and functional profiles were observed among the epiphytic bacterial and phycospheric seawater bacterial communities, which may be driven by the spatial heterogeneity of biogenic elements (e.g., organic nutrients and oxygen) among the habitats. Significant succession occurred in both the epiphytic bacterial and phycospheric seawater bacterial communities; their diversity and richness exhibited significant heterogeneity variation patterns, and their community structure became more similar in late phases. Our study revealed that macroalgal phycospheric microbial communities have a highly complex and dynamic composition and variable ecological functions, which indicate that phycospheric microorganisms are closely related to the fate of HMBs and may have the profound effect coastal biogeochemical cycles.

Iron metabolism, ferroptosis, and lncRNA in cancer: knowns and unknowns - Lei Qu; Xinyu He; Qian Tang; Xiao Fan; Jian Liu; Aifu Lin (Journal of Zhejiang University-SCIENCE B, 2022)

Paleo-karst zone and its control on reservoirs in the fourth member of the Sinian Dengying formation in the Moxi area, central Sichuan Basin - Qinyu Xia; Haijun Yan; Wei Xu; Lin Zhang; Qian Li; Wenjun Luo; Hui Deng; Xun Zhu; Xinyu Li; Jichen Yu (Carbonates and Evaporites, 2022)

Process Performance and Microbial Communities in Anaerobic Co-digestion of Sewage Sludge and Food Waste with a Lower Range of Carbon/Nitrogen Ratio - Yi Zheng; Pan Wang; Xinyu Yang; Peiru Lin; Yongjing Wang; Mengmeng Cheng; Lianhai Ren (BioEnergy Research, 2022)

Filamentous prophage capsid proteins contribute to superinfection exclusion and phage defence in Pseudomonas aeruginosa - Weiquan Wang; Yangmei Li; Kaihao Tang; Jianzhong Lin; Xinyu Gao; Yunxue Guo; Xiaoxue Wang (Environmental Microbiology, 2022)
Summary Filamentous prophages in Pseudomonas aeruginosa PAO1 are converted to superinfective phage virions during biofilm development. Superinfection exclusion is necessary for the development of resistance against superinfective phage virions in host cells. However, the molecular mechanisms underlying the exclusion of superinfective Pf phages are unknown. In this study, we found that filamentous prophage‐encoded structural proteins allow exclusion of superinfective Pf phages by interfering with type IV pilus (T4P) function. Specifically, the phage minor capsid protein pVII inhibits Pf phage adsorption by interacting with PilC and PilJ of T4P, and overproduction of pVII completely abrogates twitching motility. The minor capsid protein pIII provides partial superinfection exclusion and interacts with the PilJ and TolR/TolA proteins. Furthermore, pVII provides full host protection against infection by pilus‐dependent lytic phages, and pIII provides partial protection against infection by pilus‐independent lytic phages. Considering that filamentous prophages are common in clinical Pseudomonas isolates and their induction is often activated during biofilm formation, this study suggests the need to rethink the strategy of using lytic phages to treat P . aeruginosa biofilm‐related infections.

Identification of a Novel Species, Cladonema digitatum sp. nov. (Cnidaria: Hydrozoa: Cladonematidae), Using DNA Barcoding and Life Cycle Analyses - Xinyu Fang; Shen Lin; Yuting Zhang; Zonghua Wang; Konglin Zhou; Jianming Chen (Frontiers in Marine Science, 2022)
In this study, a new Cladonema species was identified in a laboratory aquarium in Fuzhou, China, and named Cladonema digitatum sp. nov. based on its morphological characteristics and DNA barcoding. It is distinct from other Cladonema medusae in having a manubrium with finger-like protuberances, radial canals with Y-shaped bifurcations, tentacles with 3–11 adhesive branches, and 3–7 stinging branches growing from the main branch as side branches. The validity of C. digitatum sp. nov. was supported by molecular phylogenetic analyses based on both mitochondrial cytochrome oxidase and mitochondrial 16S rRNA sequences. Similar to other Cladonema medusae, the adhesive and stinging branches of each tentacle, oral tentacle, manubrium, and gonads in C. digitatum displayed considerable phenotypic plasticity, thus making species identification based solely on morphology difficult. Although diagnostic characters such as filiform tentacles and medusa buds of hydroids and nematocysts are also useful for species identification in the genus Cladonema , related information is missing in some Cladonema species. Thus, information on the life cycle and DNA barcoding should be updated to describe new or cryptic species and to improve the taxonomy of the genus Cladonema .

LncRNA BACE1-AS promotes the progression of osteosarcoma through miR-762/SOX7 axis - Chunlei Wang; Tao Zhang; Lin Yang; Xinyu Na; Yanlong Qu (Molecular Biology Reports, 2022)

Trends and status in resources security, ecological stability, and sustainable development research: a systematic analysis - Xinyu Kang; Minxi Wang; Jing Lin; Xin Li (Environmental Science and Pollution Research, 2022)

Genome-wide identification and expression analysis of phospholipase D gene in leaves of sorghum in response to abiotic stresses - Jinpeng Wei; Wenjing Shao; Xinyu Liu; Lin He; Changjiang Zhao; Gaobo Yu; Jingyu Xu (Physiology and Molecular Biology of Plants, 2022)

Characteristics of antibiotic resistance genes in full-scale anaerobic digesters of food waste and the effects of application of biogas slurry on soil antibiotic resistance genes - Pan Wang; Yi Zheng; Peiru Lin; Xiteng Chen; Linsong Qi; Xinyu Yang; Lianhai Ren (Environmental Science and Pollution Research, 2022)

Climate warming promotes deterministic assembly of arbuscular mycorrhizal fungal communities - Xinyu Xu; Yunpeng Qiu; Kangcheng Zhang; Fei Yang; Mengfei Chen; Xi Luo; Xuebin Yan; Peng Wang; Yi Zhang; Huaihai Chen; Hui Guo; Lin Jiang; et al. (Global Change Biology, 2022)
Arbuscular mycorrhizal fungi (AMF) significantly contribute to plant resource acquisition and play important roles in mediating plant interactions and soil carbon (C) dynamics. However, it remains unclear how AMF communities respond to climate change. We assessed impacts of warming and precipitation alterations (30% increase or decrease) on soil AMF communities, and examined major ecological processes shaping the AMF community assemblage in a Tibetan alpine meadow. Our results showed that warming significantly increased root biomass, and available nitrogen (N) and phosphorus (P) in soil. While precipitation alterations increased AMF abundances, they did not significantly affect the composition or diversity of AMF communities. In contrast, warming altered the composition of AMF communities and reduced their Shannon–Wiener index and Pielou's evenness. In particular, warming shifted the AMF community composition in favor of Diversisporaceae over Glomeraceae, likely through its impact on soil N and P availability. In addition, AMF communities were phylogenetically random in the unwarmed control but clustered in warming plots, implying more deterministic community assembly under climate warming. Warming enhancement of root growth, N and P availability likely reduced plant C‐allocation to AMF, imposing stronger environmental filtering on AMF communities. We further proposed a conceptual framework that integrates biological and geochemical processes into a mechanistic understanding of warming and precipitation changes’ effects on AMF. Taken together, these results suggest that soil AMF communities may be more sensitive to warming than expected, highlighting the need to monitor their community structure and associated functional consequences on plant communities and soil C dynamics under the future warmer climate.

Recurrence of wintertime SST anomalies in the Bay of Bengal: characteristics and causes - Yun Qiu; Xinyu Lin; Chunsheng Jing (Climate Dynamics, 2021)

Pelagibacterium limicola sp. nov., isolated from a soda alkali-saline soil - Wei Wei; Kaiyan Xing; Kaili Wang; Xinyu Hu; Xin Zhang; Fan Yang; Shujing Yang; Henglin Cui; Shenkui Liu; Lin Zhu (Archives of Microbiology, 2021)

Trueperella pyogenes pyolysin inhibits lipopolysaccharide-induced inflammatory response in endometrium stromal cells via autophagy- and ATF6-dependent mechanism - Maozhen Qi; Jianguo Liu; Qingran Jiang; Hongyu Niu; Xinyu Wang; Dong Zhou; Pengfei Lin; Huatao Chen; Aihua Wang; Yaping Jin (Brazilian Journal of Microbiology, 2021)

Phytoactinopolyspora limicola sp. nov., an alkaliphilic actinomycete isolated from a soda alkali-saline soil - Wei Wei; Kaili Wang; Xinyu Hu; Sai Yang; Chunlin Zeng; Zhaozhi Hou; Shenkui Liu; Henglin Cui; Lin Zhu (Archives of Microbiology, 2021)

Effect of loading rate on the nonlinear elastic response of concrete - Xinyu Wang; Lin Song; Xicai Gao; Xu Chang (European Journal of Environmental and Civil Engineering, 2021)

TRIC-A regulates intracellular Ca2+ homeostasis in cardiomyocytes - Xinyu Zhou; Ang Li; Pei-hui Lin; Jingsong Zhou; Jianjie Ma (Pflügers Archiv - European Journal of Physiology, 2021)
Trimeric intracellular cation (TRIC) channels have been identified as monovalent cation channels that are located in the ER/SR membrane. Two isoforms discovered in mammals are TRIC-A (TMEM38a) and TRIC-B (TMEM38b). TRIC-B ubiquitously expresses in all tissues, and TRIC-B −/− mice is lethal at the neonatal stage. TRIC-A mainly expresses in excitable cells. TRIC-A −/− mice survive normally but show abnormal SR Ca 2+ handling in both skeletal and cardiac muscle cells. Importantly, TRIC-A mutations have been identified in human patients with stress-induced arrhythmia. In the past decade, important discoveries have been made to understand the structure and function of TRIC channels, especially its role in regulating intracellular Ca 2+ homeostasis. In this review article, we focus on the potential roles of TRIC-A in regulating cardiac function, particularly its effects on intracellular Ca 2+ signaling of cardiomyocytes and discuss the current knowledge gaps.

Evaluation of reanalysis surface wind products with quality-assured buoy wind measurements along the north coast of the South China Sea - Jing Cha; Xinyu Lin; Xiaogang Guo; Xiaofang Wan; Dawei You (Acta Oceanologica Sinica, 2021)

Seasonal variations in the water residence time in the Bohai Sea using 3D hydrodynamic model study and the adjoint method - Chongxin Luo; Lei Lin; Jie Shi; Zhe Liu; Zhongya Cai; Xinyu Guo; Huiwang Gao (Ocean Dynamics, 2021)

Beyond resource limitation: an expanded test of the niche dimension hypothesis for multiple types of niche axes - Xuebin Yan; Jeffrey Diez; Kailing Huang; Shaopeng Li; Xi Luo; Xinyu Xu; Fanglong Su; Lin Jiang; Hui Guo; Shuijin Hu (Oecologia, 2020)

Aberrant white matter properties of the callosal tracts implicated in girls with attention-deficit/hyperactivity disorder - Qingxia Lin; Xuan Bu; Meihao Wang; Yan Liang; Hong Chen; Weiqian Wang; Yanhong Yi; Haixi Lin; Jiaxiu Zhou; Lu Lu; Xinyu Hu; Chuang Yang; et al. (Brain Imaging and Behavior, 2020)

Assessment of Aquarius sea surface salinity with Argo in the Bay of Bengal - Xinyu Lin; Yun Qiu; Jing Cha; Xiaogang Guo (International Journal of Remote Sensing, 2019)

Correction to: Occurrence of polybrominated diphenyl ethers in floor and elevated surface house dust from Shanghai, China - Dong Niu; Yanling Qiu; Li Li; Yihui Zhou; Xinyu Du; Zhiliang Zhu; Ling Chen; Zhifen Lin (Environmental Science and Pollution Research, 2019)

PEGylated lipid microspheres loaded with cabazitaxel for intravenous administration: stability, bioavailability, antitumor efficacy, and toxicity - Yang Liu; Bin Xie; Lin Li; Xinyu Zhang; Yu Zhang; Haibing He; Tian Yin; Xing Tang; Cuifang Cai; Jingxin Gou (Drug Delivery and Translational Research, 2018)

Comparative pharmacokinetics study of five alkaloids in rat plasma and related compound–herb interactions mechanism after oral administration of Shuanghua Baihe tablets - Xinyu Zhao; Yan Wang; Lu Zheng; Chengpeng Sun; Chao Wang; Haijian Cong; Ting Xiang; Lin Zhang; Houli Zhang; Sa deng; Baojing Zhang; Bin Wu; et al. (Natural Product Research, 2018)

Occurrence of polybrominated diphenyl ethers in floor and elevated surface house dust from Shanghai, China - Dong Niu; Yanling Qiu; Li Li; Yihui Zhou; Xinyu Du; Zhiliang Zhu; Ling Chen; Zhifen Lin (Environmental Science and Pollution Research, 2018)
House dust is the main source of human exposure to flame retardants by ingestion. This study investigated the occurrence of polybrominated diphenyl ethers (PBDEs) in indoor dust from 22 houses in Shanghai, China. House dust was separately collected from the floor and elevated furnishings surface (mostly between 0.5 and 2 m height) for comparison. The concentrations of ∑ 22 PBDEs ranged from 19.4 to 3280 ng/g (with a geometric mean of 203 ng/g) and from 55.1 to 792 ng/g (with a geometric mean of 166 ng/g) in floor dust (FD) and elevated surface dust (ESD), respectively. BDE-209 was the predominant congener, accounting for about 73.1% of total PBDE burdens. In terms of congener profiles, the comparison of FD and ESD revealed no significant differences except for the ratio of BDE-47/BDE-99. ESD samples displayed a ratio of BDE-47/BDE-99 very similar to commercial penta-BDE products DE-71 while the ratio in FD was exceptionally higher. Significant correlation was found between concentrations of commercial penta-BDE compositions in FD and ESD ( p < 0.05). Except for some occasional values, PBDE levels in house dust exhibited temporal stability. Human exposure to PBDEs via dust ingestion was estimated. The highest daily intake of PBDEs was for toddlers by using 95th percentile concentrations of PBDEs via high dust ingestion in FD (23.07 ng/kg bw/day). About 20-fold difference in exposure estimates between toddlers and adults supports that toddlers are facing greater risk from indoor floor dust. Expectedly, this study highlighted the point that residents in Shanghai were exposed to low doses of PBDEs in house dust.

CSF-Based Analysis for Identification of Potential Serum Biomarkers of Neural Tube Defects - Xinyu Yan; Lixin Mai; Changchun Lin; Wenji He; Gengsheng Yin; Jiakang Yu; Lian Huang; Sanqiang Pan (Neuroscience Bulletin, 2017)

HOTAIR functions as a competing endogenous RNA to regulate PTEN expression by inhibiting miR-19 in cardiac hypertrophy - Yanjun Lai; Shuai He; Liming Ma; Hong Lin; Biyun Ren; Jing Ma; Xinyu Zhu; Shifang Zhuang (Molecular and Cellular Biochemistry, 2017)

Properties of root exudates and rhizosphere sediment of Bruguiera gymnorrhiza (L.) - Beibei Liu; Xinyu Liu; Shanshan Huo; Xin Chen; Lin Wu; Miao Chen; Kaibo Zhou; Qinfen Li; Lixu Peng (Journal of Soils and Sediments, 2017)

Endothelial progenitor cells as a possible component of stem cell niche to promote self-renewal of mesenchymal stem cells - Hongwei Zhang; Lingling Xian; Zhiyi Lin; Chaozhe Yang; Meng Zhang; Wenlei Feng; Xinyu Peng; Xueling Chen; Xiangwei Wu (Molecular and Cellular Biochemistry, 2014)